Pre- and post-coppice production and biomass chemistry of eastern cottonwood and hybrid poplars in the southeastern US - Heidi J. Renninger; Austin Himes; Courtney Siegert; Waqar Shafqat; Andrea Drager; Nicole Labbé; Keonhee Kim; Choo Hamilton (Biomass and Bioenergy, 2026)

Electron irradiation of methanol ices: Implications for organic chemical diversity on Europa's surface - Ricardo Carrasco-Herrera; Alexis Bouquet; Jennifer A. Noble; Grégoire Danger; Fabrice Duvernay; Nuri Park; Everett L. Shock; Kelly E. Miller; Christopher R. Glein; J. Hunter Waite; Christopher W. Hamilton (Icarus, 2026)

Mapping biological and chemical dimensions of antimicrobial resistance pollution and exposures due to treated wastewater discharges into US surface waters at the national scale - N.N. Khan; J. Jiang; M. Islam; H. Quon; R.L. Muenich; N. Rudko; S. Kamanmalek; J. Rice-Boayue; E. Garner; P. Westerhoff; A. Pruden; K.A. Hamilton (Environmental Pollution, 2026)

A framework for reflecting on decisions in the modelling cycle incorporating a fitness-for-purpose and pathway perspective - Moyang Liu; Serena H. Hamilton; Anthony J. Jakeman; Barbara Robson; Fateme Zare; Julien Lerat; Barry F.W. Croke (Environmental Modelling & Software, 2026)

Scanning the horizon for harmful cyanobacterial blooms - Xuexiu Chang; Hugh J. MacIsaac; Ingrid Chorus; George S. Bullerjahn; Rainer Kurmayer; Chi-Yong Ahn; Xiangzhen Kong; Steven W. Wilhelm; Susanna A. Wood; Xiangming Tang; Hans W. Paerl; Sabine Hilt; et al. (Trends in Ecology & Evolution, 2026)

Climate drove gradual rainforest transitions in Wallacea (Sulawesi, Indonesia) during the last glacial-interglacial transition (24,000 – 9,000 years BP) - Adam J. Benfield; Sarah J. Ivory; Rebecca Hamilton; Janelle Stevenson; Meredith C. Parish; Satria Bijaksana; Hendrik Vogel; James M. Russell (Quaternary Science Reviews, 2026)

Assessment of vegetation response to flow scenarios using a coupled eco-hydrological model in a semi-arid wetland - Moyang Liu; Anthony J. Jakeman; Serena H. Hamilton; Rachael F. Thomas; Julien Lerat; Barry F.W. Croke (Journal of Environmental Management, 2026)

What triggered the catastrophic 15 January 2022 Hunga eruption? - Jie Wu; Shane J. Cronin; Marco Brenna; Joali Paredes-Mariño; Sung-Hyun Park; Mila Huebsch; Alessio Pontesilli; Chris Firth; David Adams; Teresa Ubide; Kyle Hamilton; Alice MacDonald; et al. (Earth and Planetary Science Letters, 2026)

A cautionary tale of disequilibria in microlite-melt evolution driven by fast crystallization kinetics: Implications for modeling volcanic processes - Jie Wu; Alessio Pontesilli; Marco Brenna; Shane J. Cronin; Sung-Hyun Park; Joali Paredes-Mariño; Kyle Hamilton; Marta Ribó; David Adams; Mila Huebsch (Earth and Planetary Science Letters, 2026)

Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Regulation of venom composition by the Australian funnel-web spider Hadronyche infensa is achieved via compartmentalised toxin production and venom metering - David Morgenstern; Brett Hamilton; Darren Korbie; Karl R. Clauser; Brian J. Haas; Greg Bowlay; Kjetil L. Voje; Alun Jones; Deon J. Venter; Glenn F. King; Eivind A.B. Undheim (Toxicon, 2026)

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

Impact of diagenesis and acidic alteration on microbial fabrics and trace element distributions in fossilised siliceous hot spring deposits - Barbara J. Lyon; Michael C. Rowe; Andrew Langendam; Kathleen A. Campbell; Diego M. Guido; Ayrton R. Hamilton; Ema E. Nersezova; Amanda Galar; Dominique A. Stallard (Geochimica et Cosmochimica Acta, 2026)

Cleaning products and classes associated with poor respiratory health - Xin Dai; Michael J. Abramson; Garun S. Hamilton; Bruce R. Thompson; Cecilie Svanes; Geza Benke; Sonia Kaushik; Shyamali C. Dharmage; Caroline J. Lodge (Environmental Science and Pollution Research, 2026)
Exposure to cleaning products may harm the lungs, mainly through inhalation of irritants and sensitising chemicals, which can induce airway inflammation and bronchial hyperresponsiveness. Given increased use of multiple cleaning products at work and home, understanding the impacts of their interplay, rather than individual exposures, is critical but has not been investigated to date. We aim to investigate the cross-sectional association between exposure to cleaning products at home and/or in the workplace and respiratory health. We conducted a cross-sectional analysis of 318 adults from the Melbourne arm of the European Community Respiratory Health Survey (ECRHS) III. Cleaning product exposure was assessed through questionnaires, categorising participant exposure into seven product groups. Latent class analysis was used to identify exposure classes. Adjusted multivariable regression modelled associations between cleaning product classes and respiratory outcomes. We identified four classes of exposure to cleaning products: “minimal users”, “light users”, “moderate users”, “heavy users”. The most exposed “heavy user group” characterised people using many different cleaning products on a weekly basis (especially bleach, sprays, polish, solvents, acids). This class was associated with increased risks of current asthma (OR, 3.24; 95% CI 1.19–8.77), and lower post-bronchodilator FEV 1 (z-score, −0.47) and FVC (−0.46) compared with “minimal users”. This work used a data-driven latent class approach to capture real-world cleaning product use patterns and relate them to respiratory health. We found that frequent use of multiple cleaning products was linked to more asthma and lower lung function, suggesting potential combined effects. These findings highlight the need for cleaning product standards and asthma care guidelines to mitigate risks associated with cleaning products.

A catalogue of Do's and Don'ts in the modeling of environmental systems - Xifu Sun; Anthony Jakeman; Serena H. Hamilton; Volker Grimm; Randall J. Hunt; Sondoss El Sawah; Hsiao-Hsuan Wang; Barry Croke; Min Chen (Environmental Modelling & Software, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Geomorphological features of Queen Charlotte Strait, Pacific coast of Canada, and their implications for ice-sheet retreat and relative sea-level changes during the last deglaciation - Zhen Li; Cooper D. Stacey; Tark S. Hamilton; Robert Kung; J. Vaughn Barrie; Jordan Eamer; John Shaw; Randolph J. Enkin (Quaternary International, 2026)

Sensory applications of natural language processing and text analysis in practice: a review of recent literature - Kyle Hamilton; Rebekah J Miller; Jacob Lahne (Current Opinion in Food Science, 2026)

Making waves: Moving beyond the 1 in 10,000 benchmark in quantitative microbial risk assessment (QMRA) through evidence-informed risk approaches and systems decision-making - Kerry A. Hamilton; Hunter Quon; Nicholas J. Ashbolt; Patrick L. Gurian; Eva Reynaert; Charles N. Haas; Eberhard Morgenroth; Amanda M. Wilson (Water Research, 2026)

Embracing Holistic Formulation Strategies to Maximise Positive Outcomes in Aquaculture Nutrition - Artur N. Rombenso; Brett D. Glencross; Kyla Zatti; Helen Ann Hamilton; Luiz H. David; Ha H. Truong; Cedric J. Simon (Reviews in Aquaculture, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

GDF-15 - Implications for Bladder Cancer Care and Symptom Control - B. Foster; R. Vargas; P. Srinivasan; D. Koestler; M. Bechtel; J. Holzbeierlein; M. Fisch; N. Henry; J. Unger; J. Hamilton-Reeves (Journal of the Academy of Nutrition and Dietetics, 2025)

Ten-year exposure to household air pollution is associated with obstructive sleep apnoea - Yaoyao Qian; Garun S. Hamilton; Chamara V. Senaratna; Caroline J. Lodge; Michael J. Abramson; Xin Dai; Dinh S. Bui; Anurika P. De Silva; Paul S. Thomas; Bircan Erbas; Eugene H. Walters; Jennifer L. Perret; et al. (Environmental Research, 2025)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Durability of the moderate-to-heavy intensity transition can be predicted using readily available markers of physiological decoupling - Jeffrey A. Rothschild; Gabriele Gallo; Kate Hamilton; Julian D. Stevenson; Harrison Dudley-Rode; Thanchanok Charoensap; Daniel J. Plews; Andrew E. Kilding; Ed Maunder (European Journal of Applied Physiology, 2025)
Purpose To assess relationships between heart rate (HR), ventilation (̇ $$\dot V$$ V ˙ E ), and respiratory frequency (F R ) decoupling and durability of the first ventilatory threshold (VT 1 ), and the strength of practical models to predict power output at VT 1 during prolonged exercise. Methods Durability of VT 1 was assessed via measurements of power output at VT 1 before and after ~ 2.5-h of initially moderate-intensity cycling in 51 trained cyclists, as part of four studies published elsewhere. In 12 of those participants, power output at VT 1 was assessed every hour until task failure. For every assessment of power output at VT 1 , HR, F R , and $$\dot V$$ V ˙ ̇ E was measured at fixed power outputs, and thus decoupling of these variables with power output was determined. Bivariate repeated-measures correlations (r rm ) between decoupling and durability of VT 1 were assessed. Multivariable models were created to predict power output at VT 1 during prolonged exercise using generalised estimating equations. Results Negative correlations were observed between exercise-induced change in power output at VT 1 and HR (r rm = −0.76, P < 0.001) and F R (r rm = −0.40, P = 0.013) decoupling, but not $$\dot V$$ V ˙ ̇ E decoupling (r rm = −0.25, P = 0.136). The final prediction model, containing baseline VT 1 and peak oxygen uptake, F R decoupling, and an interaction between HR decoupling and exercise duration, effectively predicted real-time VT 1 (mean absolute error, ~ 7.2 W; R 2 , 0.95). Conclusion HR and/or F R decoupling during controlled training sessions may be a practically useful durability assessment. Our prediction models may be an effective means of improving within-session intensity regulation and training load monitoring.

Hypolimnetic Nutrient Subsidies to Surface Waters of a Large Lake: A Coupled Hydrodynamic Modelling and Nitrogen Isotope Field Assessment - Simon D. Stewart; David P. Hamilton; W. Troy Baisden; Piet Verburg; Kohji Muraoka; Derek C. Roberts; Brendan J. Hicks; Ian C. Duggan; Nico Donovan-Pereira (Ecosystems, 2025)
Upwelling of hypolimnetic water in lakes is important for littoral food webs as it enhances production through nutrient subsidies to surface waters. The aim of this study was to understand the role of hypolimnetic upwelling on littoral nutrient supply and diet of a freshwater unionid mussel, kākahi ( Echyridella menziesii) in an oligotrophic lake using stable isotopes (δ 15 N) as a tracer of hypolimnetic nitrogen. Upwelling events can be highly variable spatially and temporally, so to complement observations, this study used a three-dimensional hydrodynamic model (AEM3D) to simulate the transport of water from upwelling events and understand their potential impacts on kākahi. The study was conducted over an annual cycle in a large (area 620 km 2 , average depth ~ 94 m), monomictic, oligotrophic New Zealand lake. The hydrodynamic model simulations showed a strong spatial gradient. Upwelling was strongest along north-facing areas of the western shoreline owing to the prevailing south-westerly winds. The spatio-temporal distribution of nitrate-δ 15 N within the littoral zone was positively related to the rate of simulated upwelling, indicating inputs of 15 N-enriched hypolimnetic water. Kākahi δ 15 N values were positively related to upwelling averaged over an annual period, demonstrating that upwelling hotspots are ecologically meaningful. Interestingly, littoral particulate organic matter δ 15 N showed no pattern with upwelling but were homogeneous in distribution, consistent with rapid flushing with offshore water. These findings suggest that benthic littoral habitats act as hotspots for nutrient subsidies to surface waters, and that the signature of 15 N is retained over periods far longer than the duration of the upwelling by cycling within benthic primary producers and consumers.

Life and death of a sinter archive: Evolution of siliceous hot-spring deposits (Holocene) on the dynamic Paeroa Fault at Te Kopia, Taupō Volcanic Zone, New Zealand - M.C. Rowe; K.A. Campbell; A. Hamilton; Y. Jiang; J. Pelser; B. Murphy; R. Martin; K.M. Mackenzie; D.A. Stallard; B. Lyon; A. Langendam; E.E. Nersezova; et al. (Journal of Volcanology and Geothermal Research, 2025)

Molecular modeling of a novel butane-substituted chalcone: from synthesis to comprehensive electron density analysis - Aécio V. B. Oliveira; Vitor S. Duarte; Renata Layse. G. de Paula; Jaqueline E. Queiroz; Gilberto L. B. de Aquino; Hamilton B. Napolitano; Ademir J. Camargo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Parental perspectives on the use of tumor molecular profiling and germline genetic testing during their children's cancer treatment - Marcelo M. Sleiman; Muriel R. Statman; Mary Rose Yockel; Yelena P. Wu; Jada G. Hamilton; Wendy K. Kohlmann; Jennie Vagher; Soren Feola; Luke D. Maese; Jing Chen; Burton Appel; Casey J. Mehrhoff; et al. (Familial Cancer, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

A robust fourth-order finite-difference discretization for the strongly anisotropic transport equation in magnetized plasmas - L. Chacón; J. Hamilton; N. Krasheninnikova (Computer Physics Communications, 2025)

The behavioural effects of the serotonin 1A receptor agonist buspirone on cognition and emotional processing in healthy volunteers - Alexander L. W. Smith; Sorcha Hamilton; Susannah E. Murphy; Philip J. Cowen; Catherine J. Harmer (Psychopharmacology, 2025)
Rationale The 5-HT 1A receptor is expressed widely across the brain and is implicated in the mechanism of action of several therapeutics for mood disorders. However, there is limited and contradictory evidence about the role of this receptor in emotional processing and cognition. Objectives The current study tested the acute effects of a single dose of the 5-HT 1A agonist buspirone (20 mg), on a range of emotional processing (Emotional Test Battery) and cognitive (Auditory Verbal Learning Task (AVLT) and N-back) tasks in healthy, male and female volunteers (N = 62). The study was a randomised, double-blind, placebo controlled, parallel group design. Results Buspirone reduced accuracy for detection of facial expressions of disgust and increased misclassification of negative facial emotions. It had no significant effects on categorisation or recall of emotionally-valanced words. Buspirone also reduced recall accuracy in the AVLT but had no significant effect in the N-back task. Participants receiving buspirone were more likely to experience nausea, light-headedness and sleepiness. Conclusions Acute buspirone administration produced a mild impairment in verbal memory and a subtle negative bias in emotional processing in healthy volunteers. These effects are consistent with the mixed effects of buspirone on pre- and post-synaptic 5-HT 1A receptors.

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

In vivo labeling reveals that degranulation is increased under supraphysiological TCR stimulation, but not infection, in CD8+ T cells from old mice - Korbyn J. V. Dahlquist; Emma M. Dehm; Declan M. Smith; Erin D. Lucas; Mark Pierson; Sara E. Hamilton; Christina D. Camell (GeroScience, 2025)
CD8 + T cells exhibit distinct changes with aging, including a diminished naïve cell pool, an expansion of memory and exhausted cells, and altered effector molecule production, altogether leading to increased susceptibility to infection. They have reduced cytotoxicity in vivo, but increased granule content and faster cytotoxic kinetics to target cells in vitro . Whether CD8 + T cells from old mice degranulate when activated in vivo , within the aged environment, is unknown. This study investigates in vitro and in vivo degranulation of CD8 + T cells from young and old mice during supraphysiological aCD3 stimulation and two types of infection. Actively degranulating CD8 + CD44 + T cells were identified by positive labeling after a two-hour exposure to granule-specific fluorescent antibodies (CD107a and CD107b). Surprisingly, CD8 + T cells from old mice challenged with supraphysiological TCR-specific stimulation exhibited higher levels of degranulation as compared to their young counterparts. This effect is more prominent in vitro and can be partially explained by the age-specific increase in CD8 + CD44 + CD62L − cells. However, during microbial exposure or LCMV Armstrong infection, we show that CD8 + CD44 + and antigen-specific T cells from old mice have reduced degranulation, consistent with the diminished cytotoxic capacity. These data highlight the preserved intrinsic cytotoxic capacity of memory CD8 + T cells from old mice and suggest that the aged microenvironment and type of stimulation are contributing factors to the lower degranulation and cytotoxic capacity of these cells. This provides insight into the potential of increasing T cell activation to improve vaccine approaches in the elderly.

Wave-influenced connectivity and transport in submerged coral canopies - J. F. Hamilton; S. G. Monismith; J. R. Koseff (Coral Reefs, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A coupled eco-hydrological model to simulate vegetation condition from soil moisture deficit in a data-scarce semi-arid wetland - Moyang Liu; Barry F.W. Croke; Serena H. Hamilton; Julien Lerat; Anthony J. Jakeman (Ecological Modelling, 2025)

The impact of beauvericin on rainbow trout intestinal epithelial cells at different temperatures and dosing methods - Vivian R. Dayeh; Anita Solhaug; Mark E. Hamilton; Laura E. Linton; Lucy E. J. Lee; Niels C. Bols (In Vitro Cellular & Developmental Biology - Animal, 2025)

Late Cenozoic intensification of deoxygenation in the Pacific Ocean - Katrina Nilsson-Kerr; Babette A.A. Hoogakker; Dharma A. Reyes Macaya; Helge A. Winkelbauer; Elliott Hamilton; Simon Chenery; Catherine V Davis; Melanie J. Leng (Earth and Planetary Science Letters, 2025)

Embryological incubation temperature modulates behaviour in larval white sturgeon (Acispencer transmontanus) - Trevor J. Hamilton; Katherine Cheung; James Hudson; Joshua Szaszkiewicz; Erica Ingraham; Jeffrey Krook; Andréa Johnson; Brian Franczak; Steve McAdam; Colin J. Brauner (Journal of Thermal Biology, 2025)

Determinants of antimicrobial resistance in biosolids: A systematic review, database, and meta-analysis - Joanna Ciol Harrison; Grace V. Morgan; Aditya Kuppravalli; Nicole Novak; Michael Farrell; Sienna Bircher; Emily Garner; Nicholas J. Ashbolt; Amy Pruden; Rebecca L. Muenich; Treavor H. Boyer; Clinton Williams; et al. (Science of The Total Environment, 2024)

Exposure effects of synthetic glucocorticoid drugs on skeletal developmental and immune cell function in zebrafish - Charles M. Hamilton; Matthew J. Winter; Jonathan S. Ball; Maciej Trznadel; Luigi Margiotta-Casaluci; Stewart F. Owen; Charles R. Tyler (Science of The Total Environment, 2024)

Evaluating the influence of marine protected areas on surf zone fish - M. L. Marraffini; S. L. Hamilton; J. R. Marin Jarrin; M. Ladd; G. Koval; J. R. Madden; I. Mangino; L. M. Parker; K. A. Emery; K. Terhaar; D. M. Hubbard; R. J. Miller; et al. (Conservation Biology, 2024)
Marine protected areas (MPAs) globally serve conservation and fisheries management goals, generating positive effects in some marine ecosystems. Surf zones and sandy beaches, critical ecotones bridging land and sea, play a pivotal role in the life cycles of numerous fish species and serve as prime areas for subsistence and recreational fishing. Despite their significance, these areas remain understudied when evaluating the effects of MPAs. We compared surf zone fish assemblages inside and outside MPAs across 3 bioregions in California (USA). Using seines and baited remote underwater videos (BRUVs), we found differences in surf zone fish inside and outside MPAs in one region. Inside south region MPAs, we observed higher abundance (Tukey's honest significant difference [HSD] = 0.83, p = 0.0001) and richness (HSD = 0.22, p = 0.0001) in BRUVs and greater biomass (HSD = 0.32, p = 0.0002) in seine surveys compared with reference sites. Selected live‐bearing, fished taxa were positively affected by MPAs. Elasmobranchs displayed greater abundance in BRUV surveys and higher biomass in seine surveys inside south region MPAs (HSD = 0.35, p = 0.0003 and HSD = 0.23, p = 0.008, respectively). Although we observed no overall MPA signal for Embiotocidae, abundances of juvenile and large adult barred surfperch ( Amphistichus argenteus ), the most abundant fished species, were higher inside MPAs (K–S test D = 0.19, p

Ultraviolet absorbents and industrial antioxidants in seabirds, mammals, and fish from the Canadian Arctic - Ingrid-Alejandra Granados-Galvan; Jennifer F. Provencher; Mark L. Mallory; Amila De Silva; Derek C.G. Muir; Jane L. Kirk; Xiaowa Wang; Robert J. Letcher; Lisa L. Loseto; Bonnie M. Hamilton; Zhe Lu (Science of The Total Environment, 2024)

Past fire dynamics in sub-Saharan Africa during the last 25,000 years: Climate change and increasing human impacts - Laurent Bremond; Julie C. Aleman; Charly Favier; Olivier Blarquez; Daniele Colombaroli; Simon E. Connor; Carlos E. Cordova; Colin Courtney-Mustaphi; Abraham N. Dabengwa; Graciela Gil-Romera; William D. Gosling; Tamryn Hamilton; et al. (Quaternary International, 2024)

Comparison between Co(II) and Ni(II) cycling at goethite-water interfaces: Interplay with Fe(II)-catalyzed recrystallization - Zhen Wang; Maximilian Mann; Jessica L. Hamilton; Jeremy L. Wykes; Andrew J. Frierdich (Geochimica et Cosmochimica Acta, 2024)

Developing a range-wide sampling framework for endangered species: a case study with light-footed Ridgway’s rail - Bryan S. Stevens; Courtney J. Conway; Kimberly A. Sawyer; Lauren Kershek; Giselle Block; Sandra Hamilton; Rebecca Kolstrom (Biodiversity and Conservation, 2024)
Monitoring provides the foundation for evaluating recovery of endangered species, yet many species lack monitoring programs designed to integrate a species’ unique attributes, specific monitoring objectives, and principles of statistical sampling theory. We developed a framework for monitoring and assessment of endangered light-footed Ridgway’s rails ( Rallus obsoletus levipes ) across their U.S. range, relative to multi-scale recovery goals. We created spatially explicit sample units and a sampling frame covering all potential habitat to facilitate range-wide probability sampling, and also built a model of the call-broadcast process commonly used to survey marsh birds that included heterogeneity in availability for detection and conditional detectability for each bird during each survey. We used the model to simulate 96 sampling strategies that included different levels of replication, multiple approaches for sample allocation amongst strata, and both simple random and weighted probability sampling (i.e., weights proportional to local rail abundance) of sample units within strata. Effective monitoring surveyed ≥ 20–30% of the sampling frame on ≥ 3 occasions, with weighted sample selection and more targeted sampling (50% of units) for strata that are key to species recovery. We also tested Bayesian N-mixture models for estimating abundance and show that multiple models provide reasonable estimates. This work lays the foundation for statistical sampling and multi-scale population estimation for an endangered bird, and for refinement of abundance estimation models. Moreover, this work provides a replicable process for building customized and statistically defensible sampling frameworks to assess recovery of endangered species that can be used for other sensitive species.

Pywr-DRB: An open-source Python model for water availability and drought risk assessment in the Delaware River Basin - Andrew L. Hamilton; Trevor J. Amestoy; Patrick M. Reed (Environmental Modelling & Software, 2024)

Testing a rapid assessment approach for estimating ecosystem service capacity in urban green alleys - Marie C. Dade; Isabella C. Richmond; Jesse T. Rieb; Erin T.H. Crockett; Kayleigh Hutt-Taylor; Serena Sinno; Karina Benessaiah; Catherine Destrempes; Jacqueline Hamilton; Fatemeh Izadi; L. Emily Kroft; Lingshan Li; et al. (Urban Forestry & Urban Greening, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Durability of the moderate-to-heavy-intensity transition is related to the effects of prolonged exercise on severe-intensity performance - Kate Hamilton; Andrew E. Kilding; Daniel J. Plews; Mathew J. Mildenhall; Mark Waldron; Thanchanok Charoensap; Tobias H. Cox; Matthew J. Brick; Warren B. Leigh; Ed Maunder (European Journal of Applied Physiology, 2024)
Purpose Power output at the moderate-to-heavy-intensity transition decreases during prolonged exercise, and resilience to this has been termed ‘durability’. The purpose of this study was to assess the relationship between durability and the effect of prolonged exercise on severe-intensity performance, and explore intramuscular correlates of durability. Methods On separate days, 13 well-trained cyclists and triathletes (V̇O 2 peak, 57.3 ± 4.8 mL kg −1 min −1 ; training volume, 12 ± 2.1 h week −1 ) undertook an incremental test and 5-min time trial (TT) to determine power output at the first ventilatory threshold (VT 1 ) and severe-intensity performance, with and without 150-min of prior moderate-intensity cycling. A single resting vastus lateralis microbiopsy was obtained. Results Prolonged exercise reduced power output at VT 1 (211 ± 40 vs. 198 ± 39 W, ∆ -13 ± 16 W, ∆ -6 ± 7%, P = 0.013) and 5-min TT performance (333 ± 75 vs. 302 ± 63 W, ∆ -31 ± 41 W, ∆ -9 ± 10%, P = 0.017). The reduction in 5-min TT performance was significantly associated with durability of VT 1 (r s = 0.719, P = 0.007). Durability of VT 1 was not related to vastus lateralis carnosine content, citrate synthase activity, or complex I activity ( P > 0.05). Conclusion These data provide the first direct support that durability of the moderate-to-heavy-intensity transition is an important performance parameter, as more durable athletes exhibited smaller reductions in 5-min TT performance following prolonged exercise. We did not find relationships between durability and vastus lateralis carnosine content, citrate synthase activity, or complex I activity.

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Does salinity mediate the toxicity of perfluorooctanesulfonic acid (PFOS) in an estuarine fish? - Lucy E. Burcham; Tyler D. Hoskins; Elizabeth B. Allmon; Meredith N. Scherer; Anna G. Bushong; Matthew T. Hamilton; Sini Macheri; Grace S. Coogan; Youn J. Choi; Linda S. Lee; Maria S. Sepúlveda (Marine Pollution Bulletin, 2024)

Detection of viable Toxoplasma gondii in retail venison - J. Thomson; M. Joeres; G. Schares; E.A. Innes; C.M. Hamilton (Food Control, 2024)

Composition and speciation of volcanic volatiles on the Moon - Matthew Varnam; Christopher W. Hamilton; Igor Aleinov; Jessica J. Barnes (Icarus, 2024)

Variations in antimicrobial resistance genes present in the rectal faeces of seals in Scottish and Liverpool Bay coastal waters - Eleanor Watson; Scott Hamilton; Nuno Silva; Simon Moss; Craig Watkins; Johanna Baily; Thorsten Forster; Ailsa J. Hall; Mark P. Dagleish (Environmental Pollution, 2024)

Migration of transition metals and potential for carbon mineralization during acid leaching of processed kimberlite from Venetia diamond mine, South Africa - Baolin Wang; Nina Zeyen; Sasha Wilson; Makoto J. Honda-McNeil; Jessica L. Hamilton; Konstantin Von Gunten; Daniel S. Alessi; Thomas R. Jones; David J. Paterson; Gordon Southam (Applied Geochemistry, 2024)

Dispersal patterns of sandfish (Holothuria scabra) larvae in Manus Province, Papua New Guinea - Peter Waldie; David A. Feary; Michael Bode; Manuai Matawai; Hugo B. Harrison; Michael L. Berumen; Chris Molai; Maunoa Karo; Richard J. Hamilton (Frontiers in Marine Science, 2024)
In many tropical nations, coastal communities seek to manage their sea cucumber fisheries by establishing locally managed marine areas on their traditional fishing grounds. These managed areas can protect spawning stocks, however the extent to which they help to replenish nearby sea cucumber fisheries is debated, as nothing is known about the scales at which sea cucumber larvae disperse. In this study, we used genetic parentage analyses and statistical modelling to provide the first empirical measure of larval dispersal patterns for a sea cucumber species. We analysed tissue samples from 765 adult and 827 juvenile sandfish ( Holothuria scabra ) collected from five traditional fishing grounds of the Titan tribe, from Manus Province, Papua New Guinea. All adults were sampled from the Pere fishing grounds (the larval source area), with juveniles sampled from the Pere, Mbunai, Tawi, Timonai and Mbuke fishing grounds. Parentage analysis identified 15 juveniles that were the offspring of parents sampled from Pere fishing grounds, with six of these juveniles located in the same fishing grounds as their parents. The best-fit larval dispersal kernel predicted that the average H. scabra larvae travelled 15 km from its spawning location, with 50% of larvae settling within 6.7 km of their parents and 95% of larvae settling within 59 km of their parents. These results suggest that the Titan tribes’ desire to protect their H. scabra spawning stocks by establishing a network of locally managed marine areas across 65 km of continuous coastline is a culturally appropriate strategy, which has merit from both an ecological and fisheries standpoint.

Exploring vaginal discharge scoring to assess clinical metritis severity: Comparison between intrauterine dextrose and systemic antibiotics treatments - J. Hamilton; E. Jimenez; P. Zarei; J. Lection; R. Sorto; E. Hovingh; M. Martinez; S. Bas; A.A. Barragan (The Veterinary Journal, 2024)

Degradation of the 2014–2015 Holuhraun vent-proximal edifice in Iceland - S. S. Sutton; J. A. Richardson; P. L. Whelley; S. P. Scheidt; C. W. Hamilton (Bulletin of Volcanology, 2024)
The earliest stages of volcanic vent degradation are rarely measured, leaving a gap in the knowledge that informs landform degradation models of cinder cones and other monogenetic vent structures. We documented the initial degradation of a 500-m-long spatter rampart at the primary vent of the 2014–2015 Holuhraun eruption in northern Iceland with high-resolution topographic change maps derived from terrestrial laser scanning (TLS) and photogrammetric surveys using an unoccupied aircraft system (UAS). Topographic differencing shows a total negative volume change of 42,637 m 3 , and a total positive volume change (basal deposition) of 10,304 m 3 (primarily as deposition at the base of steeply sloping surfaces). Two distinct styles of volume changes were observed on the interior and exterior of the spatter rampart. Material on the interior of the vent was removed from oversteepened slopes by discrete rockfalls, while diffusive processes were qualitatively evident on the exterior slopes. We propose a novel conceptual landform evolution model for spatter ramparts that combines rockfall processes on the interior walls, diffusive gravitational sliding on the exterior slopes, and incorporates cooling contraction and compaction over the entire edifice to describe the observed modes of topographic change during the onset of degradation. Potential hazards at fresh spatter ramparts are rockfalls at high slope areas of the vent interior walls where contacts between spatter clasts are prone to weakening by fumarolic activity, weathering, and settling. To capture such hazards, our data suggest a cadence for monitoring changes yearly for the first few years post-eruption, and at longer intervals thereafter.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

A microbial risk assessor's guide to Valley Fever (Coccidioides spp.): Case study and review of risk factors - David Kahn; William Chen; Yarrow Linden; Karalee A. Corbeil; Sarah Lowry; Ciara A. Higham; Karla S. Mendez; Paige Burch; Taylor DiFondi; Marc Verhougstraete; Anneclaire J. De Roos; Charles N. Haas; et al. (Science of The Total Environment, 2024)

Reductive sorption of vanadium by iron monosulfide in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; Nicholas J.C. Doriean; David T. Welsh; Joseph A. Otte; Jessica Hamilton; Donald E. Canfield; Yun Wang; Enzo Lombi; William W. Bennett (Chemical Geology, 2024)

Synthesis, characterization, and supramolecular analysis of a novel chalcone derivative: exploring nonlinear optical applications - Luiz B. Costa; Cristiane A. F. E. Santos; Jaqueline E. Queiroz; Antônio S. N. Aguiar; Lóide O. Sallum; Jean M. F. Custodio; Gilberto L. B. Aquino; Ademir J. Camargo; Clodoaldo Valverde; Hamilton B. Napolitano (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Shorebird Abundance is Associated with Nutritional Quality of Intertidal Biofilm on the Fraser River Estuary - Mark C. Drever; Matthew J. Mogle; Tristan J. Douglas; Scott A. Flemming; Diana J. Hamilton; Justin D. Liefer; Robert W. Elner (Estuaries and Coasts, 2024)
Dense congregations of shorebirds forage on tidal flats during long-distance migration, and their abundance is presumed to mirror the underlying ecological conditions. We quantified the nutritional content of intertidal biofilm (a thin layer of microalgae, bacteria, and other microorganisms embedded in a mucilaginous matrix that sits on the surface of tidal flats) to assess whether biofilm biomass, macronutrient content (lipid, protein, and carbohydrate), or both, provide a measure of habitat quality for migrating shorebirds. We compared shorebird use, biofilm biomass, macronutrient content, and stable isotope signatures at two mudflats on the Fraser River estuary, British Columbia, Canada, during summer 2020 (southward migration) and spring 2021 (northward migration). The abundances of Western Sandpiper ( Calidris mauri ) and Dunlin ( Calidris alpina ) were consistently higher (6–100×) at Brunswick Point relative to the Iona Foreshore site during both migration periods. Biofilm biomass (chlorophyll a ) was 2× higher at Brunswick Point than Iona Foreshore during southward migration, and was similar between sites during northward migration, suggesting biofilm biomass alone was not a main determinant of shorebird use of these sites. Macronutrient content (lipid, protein, and carbohydrate) in intertidal biofilm was 1.4× to 3.8× higher at Brunswick Point than Iona Foreshore during both migration periods, indicating an association between macronutrient content and shorebird use. Carbohydrate content was higher during southward migration at both tidal flats, whereas protein and lipid content at Iona Foreshore did not show significant differences between years or migration periods. Carbon and nitrogen stable isotope signatures during spring 2021 did not differ between the two sites, suggesting that nutrients had similar relative inputs from marine and freshwater sources. While our comparative study does not eliminate alternative explanations that might act concomitantly (e.g., invertebrate abundance, predation risk, and disturbance), our results are consistent with the hypothesis that small-bodied shorebirds are more abundant at sites where intertidal biofilm has high macronutrient content. The latter can vary in complex ways depending on the taxonomic composition and physiological state of the microphytobenthos. Thus, the nutritional “quality” of intertidal biofilm can serve as a useful measure for determining restoration goals for tidal flats or assessing coastal areas for development projects.

Treatment with PB125® Increases Femoral Long Bone Strength in 15-Month-Old Female Hartley Guinea Pigs - K. M. Andrie; D. R. Palmer; O. Wahl; S. Bork; M. Campbell; M. A. Walsh; J. Sanford; R. V. Musci; Karyn L. Hamilton; Kelly S. Santangelo; Christian M. Puttlitz (Annals of Biomedical Engineering, 2024)

Synthetic asphaltene for green carbon material - Masato Morimoto; David E. Scott; Robin J. Hamilton; Jeffrey M. Stryker; Rik R. Tykwinski; Murray R. Gray (Fuel, 2024)

Genetic sex determination improves Canadian Atlantic salmon ( Salmo salar ) population assessments - Martha J. Robertson; Sarah J. Lehnert; Nicholas I. Kelly; Lorraine C. Hamilton; Ross A. Jones; Alex L. Levy; Rebecca Poole; Chantelle M. Burke; Steven J. Duffy; Amber Messmer; Ian R. Bradbury (Fisheries Management and Ecology, 2024)
Estimating egg deposition for Atlantic salmon population assessments is made difficult by their lack of sexual dimorphism prior to the autumn spawning season. We quantified the effect of sex misclassification from subjective examination of external morphology on egg deposition estimates in four Atlantic salmon populations across multiple years. Sex classification of Canadian salmon using the genetic sex marker ( sd Y) was accurate (>97%), whereas sex classification based on subjective examination of external morphology was inaccurate, with misclassification rates dependent on sea age, life history, and sampling season. Sex misclassification led to annual egg deposition estimates that ranged from −36% to +56%. We found that sex could not be discriminated based on measures of external morphology.

Assessing the contribution of hydrologic and climatic factors on vegetation condition changes in semi-arid wetlands: An analysis for the Narran Lakes - Moyang Liu; Serena H. Hamilton; Anthony J. Jakeman; Julien Lerat; Callum Savage; Barry F.W. Croke (Ecological Modelling, 2024)

Predictive geochemical mapping using machine learning in western Kenya - Olivier S. Humphrey; Mark Cave; Elliott M. Hamilton; Odipo Osano; Diana Menya; Michael J. Watts (Geoderma Regional, 2023)

Reductive sorption of vanadium by green rust in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; David Welsh; Jessica Hamilton; Yun Wang; Jessica White; Donald E. Canfield; Enzo Lombi; William W. Bennett (Geochimica et Cosmochimica Acta, 2023)

Metagenomic analysis of ethylene glycol contamination in anaerobic digestion - Gabrielle R. Joslin; Daniel G. Barber; Lindsay Aston; Ping Liu; Olukayode Kuloyo; Kangsa Oentoro; Jiayi Liu; Ashley V. Baugh; Jeffrey R. Fedenko; Ioannis Melas; Phillip G. Hamilton; Damian J. Allen; et al. (Bioresource Technology, 2023)

African American Women Breast Cancer Survivors: Coping with the COVID-19 Pandemic - Jill B. Hamilton; Autherine N. Abiri; Charlyne A. Nicolas; Kayoll Gyan; Rasheeta D. Chandler; Valarie C. Worthy; Ernest J. Grant (Journal of Cancer Education, 2023)

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

Enhanced skeletal muscle contractile function and corticospinal excitability precede strength and architectural adaptations during lower-limb resistance training - Matthew T. Wilson; Angus M. Hunter; Malcolm Fairweather; Stewart Kerr; D. Lee Hamilton; Lewis J. Macgregor (European Journal of Applied Physiology, 2023)
Purpose Evolving investigative techniques are providing greater understanding about the early neuromuscular responses to resistance training among novice exercisers. The aim of this study was to investigate the time-course of changes in muscle contractile mechanics, architecture, neuromuscular, and strength adaptation during the first 6-weeks of lower-limb resistance training. Methods Forty participants: 22 intervention (10 males/12 females; 173.48 ± 5.20 cm; 74.01 ± 13.13 kg) completed 6-week resistance training, and 18 control (10 males/8 females; 175.52 ± 7.64 cm; 70.92 ± 12.73 kg) performed no resistance training and maintained their habitual activity. Radial muscle displacement (Dm) assessed via tensiomyography, knee extension maximal voluntary contraction (MVC), voluntary activation (VA), corticospinal excitability and inhibition via transcranial magnetic stimulation, motor unit (MU) firing rate, and muscle thickness and pennation angle via ultrasonography were assessed before and after 2, 4, and 6-weeks of dynamic lower-limb resistance training or control. Results After 2-weeks training, Dm reduced by 19–25% in the intervention group; this was before any changes in neural or morphological measures. After 4-weeks training, MVC increased by 15% along with corticospinal excitability by 16%; however, there was no change in VA, corticospinal inhibition, or MU firing rate. After 6-weeks training there was further MVC increase by 6% along with muscle thickness by 13–16% and pennation angle by 13–14%. Conclusion Enhanced contractile properties and corticospinal excitability occurred before any muscle architecture, neural, and strength adaptation. Later increases in muscular strength can be accounted for by architectural adaptation.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Artisanal gold mining in Kakamega and Vihiga counties, Kenya: potential human exposure and health risk - Maureene Auma Ondayo; Michael J. Watts; Elliott M. Hamilton; Clive Mitchell; Joseph Mankelow; Odipo Osano (Environmental Geochemistry and Health, 2023)
Artisanal and small-scale gold mining (ASGM) represents 20% of gold supply and 90% of gold mining workforce globally, which operates in highly informal setups. Pollutants from mined ores and chemicals introduced during gold processing pose occupational and inadvertent health risks to the extent that has not been well elucidated in Africa. Trace and major elements were analysed using inductively coupled plasma mass spectrometry in soil, sediment and water samples from 19 ASGM villages in Kakamega and Vihiga counties. Associated health risks for residents and ASGM workers were assessed. This paper focuses on As, Cd, Cr, Hg, Ni and Pb for which 96% of soil samples from mining and ore processing sites had As concentrations up to 7937 times higher than the US EPA 12 mg kg −1 standard for residential soils. Soil Cr, Hg and Ni concentrations in 98%, 49% and 68% of the samples exceeded respective USEPA and CCME standards, with 1–72% bioaccessibility. Twenty-five percentage of community drinking water sources were higher than the WHO 10 µg L −1 drinking water guideline. Pollution indices indicated significant enrichment and pollution of soils, sediment and water in decreasing order of As > Cr > Hg > Ni > Pb > Cd. The study revealed increased risks of non-cancer health effects (98.6) and cancer in adults (4.93 × 10 −2 ) and children (1.75 × 10 −1 ). The findings will help environment managers and public health authorities better understand the potential health risks in ASGM and support evidence-based interventions in ASGM processes, industrial hygiene and formulation of public health policy to protect residents and ASGM workers’ health in Kenya.

ACMT Position Statement: End the Use of the Term “Excited Delirium” - Andrew I. Stolbach; Paul I. Dargan; Howard A. Greller; Richard J. Hamilton; Kelly Johnson-Arbor; Brian Patrick Murray; Daniel Ovakim; Laura Tormoehlen; Lewis S. Nelson; Sukhshant Atti; Jeffrey N. Bernstein; Caitlin Bonney; et al. (Journal of Medical Toxicology, 2023)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

Effects of ocean acidification on dopamine-mediated behavioral responses of a coral reef damselfish - Trevor J. Hamilton; Martin Tresguerres; Garfield T. Kwan; Joshua Szaskiewicz; Brian Franczak; Tyler Cyronak; Andreas J. Andersson; David I. Kline (Science of The Total Environment, 2023)

Tritium across the hydrologic systems of southern Ontario, Canada: implications for groundwater age dating in the Great Lakes Basin - E. H. Priebe; S. M. Hamilton; A. Lemieux; D. J. Rowan; I. D. Clark (Hydrogeology Journal, 2023)

Evidence for ecotone speciation across an African rainforest‐savanna gradient - Adam H. Freedman; Ryan J. Harrigan; Ying Zhen; Alison M. Hamilton; Thomas B. Smith (Molecular Ecology, 2023)
Accelerating climate change and habitat loss make it imperative that plans to conserve biodiversity consider species' ability to adapt to changing environments. However, in biomes where biodiversity is highest, the evolutionary mechanisms responsible for generating adaptative variation and, ultimately, new species are frequently poorly understood. African rainforests represent one such biome, as decadal debates continue concerning the mechanisms generating African rainforest biodiversity. These debates hinge on the relative importance of geographic isolation versus divergent natural selection across environmental gradients. Hindering progress is a lack of robust tests of these competing hypotheses. Because African rainforests are severely at‐risk due to climate change and other anthropogenic activities, addressing this long‐standing debate is critical for making informed conservation decisions. We use demographic inference and allele frequency‐environment relationships to investigate mechanisms of diversification in an African rainforest skink, Trachylepis affinis , a species inhabiting the gradient between rainforest and rainforest‐savanna mosaic (ecotone). We provide compelling evidence of ecotone speciation, in which gene flow has all but ceased between rainforest and ecotone populations, at a level consistent with infrequent hybridization between sister species. Parallel patterns of genomic, morphological, and physiological divergence across this environmental gradient and pronounced allele frequency‐environment correlation indicate speciation is mostly probably driven by ecological divergence, supporting a central role for divergent natural selection. Our results provide strong evidence for the importance of ecological gradients in African rainforest speciation and inform conservation strategies that preserve the processes that produce and maintain biodiversity.

Viral Disease Goes Viral: Characterizing How Cancer Patients Use Internet Resources for COVID-19 Information - Ruijia Jin; Howard J. Lim; Sarah Hamilton; Paris-Ann Ingledew (Journal of Cancer Education, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

Quantification and uncertainty of root growth stimulation by elevated CO2 in a mature temperate deciduous forest - Clare Ziegler; Aleksandra Kulawska; Angeliki Kourmouli; Liz Hamilton; Zongbo Shi; A. Rob MacKenzie; Rosemary J. Dyson; Iain G. Johnston (Science of The Total Environment, 2023)

Social dominance and rainfall predict telomere dynamics in a cooperative arid‐zone bird - Emma M. Wood; Pablo Capilla‐Lasheras; Dominic L. Cram; Lindsay A. Walker; Jenny E. York; Anke Lange; Patrick B. Hamilton; Charles R. Tyler; Andrew J. Young (Molecular Ecology, 2022)
In many vertebrate societies dominant individuals breed at substantially higher rates than subordinates, but whether this hastens ageing remains poorly understood. While frequent reproduction may trade off against somatic maintenance, the extraordinary fecundity and longevity of some social insect queens highlight that breeders need not always suffer more rapid somatic deterioration than their nonbreeding subordinates. Here, we used extensive longitudinal assessments of telomere dynamics to investigate the impact of dominance status on within‐individual age‐related changes in somatic integrity in a wild social bird, the white‐browed sparrow‐weaver ( Plocepasser mahali ). Dominant birds, who monopolise reproduction, had neither shorter telomeres nor faster telomere attrition rates over the long‐term (1–5 years) than their subordinates. However, over shorter (half‐year) time intervals dominants with shorter telomeres showed lower rates of telomere attrition (and evidence suggestive of telomere lengthening), while the same was not true among subordinates. Dominants may therefore invest more heavily in telomere length regulation (and/or somatic maintenance more broadly); a strategy that could mitigate the long‐term costs of reproductive effort, leaving their long‐term telomere dynamics comparable to those of subordinates. Consistent with the expectation that reproduction entails short‐term costs to somatic integrity, telomere attrition rates were most severe for all birds during the breeding seasons of wetter years (rainfall is the key driver of reproductive activity in this arid‐zone species). Our findings suggest that, even in vertebrate societies in which dominants monopolise reproduction, dominants may experience long‐term somatic integrity trajectories indistinguishable from those of their nonreproductive subordinates.

A downscaled economic model validated and applied to sediment management projects in Ireland and Scotland - J. Harrington; R. O.’ Sullivan; A. Hamilton; R. Lord; K. Torrance; A. Wijdeveld; T. Debuigne; E. Masson; B. Batel (Journal of Soils and Sediments, 2022)
Purpose This paper presents a regionally downscaled economic model developed to assess the impacts of the management of dredged sediments on Gross Domestic Product (GDP) and jobs created; the model is validated and applied using real project data from sediment management projects in Ireland and Scotland. The model provides significant insight into and allows impact analysis for the economic aspect of sediment management projects with the potential to facilitate and inform stakeholders across the sediment management sector. Methods The economic model facilitates regional analysis of the impacts of sediment management projects on GDP and job creation for direct, indirect and induced effects. Methods for estimating the economic induced impacts are based on industry-specific type I and type II economic multipliers and coefficients, derived for the EU Interreg SURICATES partner countries (Ireland, Scotland, France and the Netherlands) using symmetric input–output tables and application of the open Leontief model and based on available economic data for the identified countries. The model is applied to sediment management projects in Ireland (a harbour development project at Castletownbere) and in Scotland (a bioremediation project at Falkirk). Model results are compared to project data for direct contribution to GDP and direct jobs created, and the model also estimates the indirect and induced economic project impacts. The model has been applied to undertake sensitivity analyses and compare different sediment management options. Results Model results provide a satisfactory comparison to real project data for direct cost and jobs created. Indirect economic benefits for GDP and employment created were estimated from 47 to 53% of direct impacts . The model has been applied to undertake sensitivity analyses and assess a range of different site-specific sediment management options with indirect economic impacts ranging from 42 to 53% of direct impacts. Conclusions The economic model results are compared to real project economic data, the validation exercise proving satisfactory with promising results. Sensitivity analyses and site-specific sediment management options have been assessed. The positive economic impacts of the Castletownbere Harbour project in particular are evident. These results highlight the potentially different economic impacts of the implementation of different sediment management options and in different regions and countries. The model allows the quantification of the economic benefits of sediment management projects. The model provides significant insight into and allows impact analysis for the economic aspect of sediment management projects and has the potential to facilitate and inform stakeholders and decision-makers across the sector.

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Climate impacts alter fisheries productivity and turnover on coral reefs - Mark Hamilton; James P. W. Robinson; Cassandra E. Benkwitt; Shaun K. Wilson; M. Aaron MacNeil; Ameer Ebrahim; Nicholas A. J. Graham (Coral Reefs, 2022)
Alteration of benthic reef habitat after coral bleaching and mortality induces changes in fish assemblages, with implications for fisheries. Our understanding of climate impacts to coral reef fisheries is largely based on fish abundance and biomass. The rates at which biomass is produced and replenished (productivity and turnover) are also important to sustaining fisheries, yet the responses of these metrics following bleaching are largely unknown. Here, we examine changes in fish productivity and turnover after mass coral bleaching events in Seychelles, on reefs that were recovering to coral-dominated habitats and those that shifted to macroalgae-dominated regimes. Productivity of fish assemblages increased on all recovering reefs, particularly on fished reefs resulting in levels similar to protected reefs 19 years after bleaching. Herbivore-detritivores, such as scraping and excavating parrotfish, appeared to drive biomass production through increased abundance on recovering reefs. Productivity on regime-shifted reefs remained stable at 1994 levels in fished areas, with increases observed on protected reefs. Large increases in browser productivity (particularly on protected reefs), combined with increases for invertivores, maintained post-bleaching productivity on macroalgal reefs. For all diet groups, net turnover was generally higher on fished regime-shifted reefs than on recovering reefs, suggesting fish biomass is more readily replenished on macroalgal reefs. Reef structural complexity was a positive predictor of productivity for all diet groups. These findings indicate that post-bleaching reef fish productivity is strongly influenced by benthic recovery trajectories, and demonstrates the importance of herbivore and invertivore species in sustaining small-scale inshore fisheries following climatic disturbances.

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Artificial intelligence for right whale photo identification: from data science competition to worldwide collaboration - Christin Khan; Drew Blount; Jason Parham; Jason Holmberg; Philip Hamilton; Claire Charlton; Fredrik Christiansen; David Johnston; Will Rayment; Steve Dawson; Els Vermeulen; Victoria Rowntree; et al. (Mammalian Biology, 2022)
Photo identification is an important tool in the conservation management of endangered species, and recent developments in artificial intelligence are revolutionizing existing workflows to identify individual animals. In 2015, the National Oceanic and Atmospheric Administration hosted a Kaggle data science competition to automate the identification of endangered North Atlantic right whales ( Eubalaena glacialis ). The winning algorithms developed by Deepsense.ai were able to identify individuals with 87% accuracy using a series of convolutional neural networks to identify the region of interest, create standardized photographs of uniform size and orientation, and then identify the correct individual. Since that time, we have brought in many more collaborators as we moved from prototype to production. Leveraging the existing infrastructure by Wild Me, the developers of Flukebook, we have created a web-based platform that allows biologists with no machine learning expertise to utilize semi-automated photo identification of right whales. New models were generated on an updated dataset using the winning Deepsense.ai algorithms. Given the morphological similarity between the North Atlantic right whale and closely related southern right whale ( Eubalaena australis ), we expanded the system to incorporate the largest long-term photo identification catalogs around the world including the United States, Canada, Australia, South Africa, Argentina, Brazil, and New Zealand. The system is now fully operational with multi-feature matching for both North Atlantic right whales and southern right whales from aerial photos of their heads (Deepsense), lateral photos of their heads (Pose Invariant Embeddings), flukes (CurvRank v2), and peduncle scarring (HotSpotter). We hope to encourage researchers to embrace both broad data collaborations and artificial intelligence to increase our understanding of wild populations and aid conservation efforts.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Coupled changes in pH, temperature, and dissolved oxygen impact the physiology and ecology of herbivorous kelp forest grazers - Emily M. Donham; Lauren T. Strope; Scott L. Hamilton; Kristy J. Kroeker (Global Change Biology, 2022)
Understanding species’ responses to upwelling may be especially important in light of ongoing environmental change. Upwelling frequency and intensity are expected to increase in the future, while ocean acidification and deoxygenation are expected to decrease the pH and dissolved oxygen (DO) of upwelled waters. However, the acute effects of a single upwelling event and the integrated effects of multiple upwelling events on marine organisms are poorly understood. Here, we use in situ measurements of pH, temperature, and DO to characterize the covariance of environmental conditions within upwelling‐dominated kelp forest ecosystems. We then test the effects of acute (0–3 days) and chronic (1–3 months) upwelling on the performance of two species of kelp forest grazers, the echinoderm, Mesocentrotus franciscanus , and the gastropod, Promartynia pulligo . We exposed organisms to static conditions in a regression design to determine the shape of the relationship between upwelling and performance and provide insights into the potential effects in a variable environment. We found that respiration, grazing, growth, and net calcification decline linearly with increasing upwelling intensity for M . francicanus over both acute and chronic timescales. Promartynia pulligo exhibited decreased respiration, grazing, and net calcification with increased upwelling intensity after chronic exposure, but we did not detect an effect over acute timescales or on growth after chronic exposure. Given the highly correlated nature of pH, temperature, and DO in the California Current, our results suggest the relationship between upwelling intensity and growth in the 3‐month trial could potentially be used to estimate growth integrated over long‐term dynamic oceanographic conditions for M . franciscanus . Together, these results indicate current exposure to upwelling may reduce species performance and predicted future increases in upwelling frequency and intensity could affect ecosystem function by modifying the ecological roles of key species.

Assessment of bioaccessibility and health risk of mercury within soil of artisanal gold mine sites, Niger, North-central part of Nigeria - Abiodun M. Odukoya; Bernard Uruowhe; Michael J. Watts; Elliott M. Hamilton; Andrew L. Marriott; Babajide Alo; Nnamdi C. Anene (Environmental Geochemistry and Health, 2022)

Effects of grazing on plant communities and successional processes vary along an aridity gradient at a northern temperate grassland - Nicholas P. Hamilton; Paul T. Sanborn; Philip J. Burton (Plant Ecology, 2022)

Venoms for all occasions: The functional toxin profiles of different anatomical regions in sea anemones are related to their ecological function - Lauren M. Ashwood; Eivind A. B. Undheim; Bruno Madio; Brett R. Hamilton; Marymegan Daly; David A. Hurwood; Glenn F. King; Peter J. Prentis (Molecular Ecology, 2022)
The phylum Cnidaria is the oldest extant venomous group and is defined by the presence of nematocysts, specialized organelles responsible for venom production and delivery. Although toxin peptides and the cells housing nematocysts are distributed across the entire animal, nematocyte and venom profiles have been shown to differ across morphological structures in actiniarians. In this study, we explore the relationship between patterns of toxin expression and the ecological roles of discrete anatomical structures in Telmatactis stephensoni . Specifically, using a combination of proteomic and transcriptomic approaches, we examined whether there is a direct correlation between the functional similarity of regions and the similarity of their associated toxin expression profiles. We report that the regionalization of toxin production is consistent with the partitioning of the ecological roles of venom across envenomating structures, and that three major functional regions are present in T . stephensoni : tentacles, epidermis and gastrodermis. Additionally, we find that most structures that serve similar functions not only have comparable putative toxin profiles but also similar nematocyst types. There was no overlap in the putative toxins identified using proteomics and transcriptomics, but the expression patterns of specific milked venom peptides were conserved across RNA‐sequencing and mass spectrometry imaging data sets. Furthermore, based on our data, it appears that acontia of T . stephensoni may be transcriptionally inactive and only mature nematocysts are present in the distal portions of the threads. Overall, we find that the venom profile of different anatomical regions in sea anemones varies according to its ecological functions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The relevance of pedigrees in the conservation genomics era - Stephanie J. Galla; Liz Brown; Yvette Couch‐Lewis (Ngāi Tahu: Te Hapū o Ngāti Wheke, Ngāti Waewae); Ilina Cubrinovska; Daryl Eason; Rebecca M. Gooley; Jill A. Hamilton; Julie A. Heath; Samantha S. Hauser; Emily K. Latch; Marjorie D. Matocq; Anne Richardson; et al. (Molecular Ecology, 2022)
Over the past 50 years conservation genetics has developed a substantive toolbox to inform species management. One of the most long‐standing tools available to manage genetics—the pedigree—has been widely used to characterize diversity and maximize evolutionary potential in threatened populations. Now, with the ability to use high throughput sequencing to estimate relatedness, inbreeding, and genome‐wide functional diversity, some have asked whether it is warranted for conservation biologists to continue collecting and collating pedigrees for species management. In this perspective, we argue that pedigrees remain a relevant tool, and when combined with genomic data, create an invaluable resource for conservation genomic management. Genomic data can address pedigree pitfalls (e.g., founder relatedness, missing data, uncertainty), and in return robust pedigrees allow for more nuanced research design, including well‐informed sampling strategies and quantitative analyses (e.g., heritability, linkage) to better inform genomic inquiry. We further contend that building and maintaining pedigrees provides an opportunity to strengthen trusted relationships among conservation researchers, practitioners, Indigenous Peoples, and Local Communities.

Fish Assemblages in a Small Mangrove System on Príncipe Island, Gulf of Guinea - Mariana Cravo; Armando J. Almeida; Hamilton Lima; João Azevedo e Silva; Salomão Bandeira; Vilma Machava-António; José Paula (Frontiers in Marine Science, 2021)
Mangroves are highly productive ecosystems with complex adaptations to the transition between freshwater and sea. Mangroves function as nursery habitats for many organisms, providing protection and food sources for early developmental stages of crustaceans and fish, helping to maintain adjacent marine stocks. Mangroves in São Tomé and Príncipe remain poorly studied. This study addresses the importance of a small mangrove stand to ichthyofauna. The main goal of the study was to describe the fish assemblages of the Praia Salgada mangrove stand on Príncipe Island, and assess if variations in the season, tide, and mangrove zone affected fish distribution. Fish assemblages were sampled with mosquito nets during the rainy and dry seasons, and neap and spring tides, while environmental parameters such as water depth, temperature, pH, and salinity measurements were taken. The characteristics of the water column were affected by a sandbank that developed between sampling seasons, impacting on the dynamics of the water and biological exchanges between the mangrove stand and the adjacent marine environment. The study identified 14 fish species occurring in the Praia Salgada mangrove stand from a total of 772 specimens caught. Five species were recorded for the first time as occurring in the country’s mangrove areas, namely Caranx latus , Ethmalosa fimbriata , Mugil curema , Gobioides cf. africanus , and Citharus cf. linguatula . Most of the reported species are of commercial interest, and were predominantly juveniles, suggesting that the mangrove ecosystem provides a nursery function for several species. Some species revealed preferences for either the upper or lower part of the mangrove forest. The size of fish sampled tended to be bigger during the dry season, especially for the Mugilidae, Aplocheilichthys spilauchen and Gobiidae groups. E. fimbriata and Eucinostomus melanopterus displayed similar sizes between seasons. The average quantity of fish caught per day in the rainy season was three times higher than in the dry season. The fish species distribution in the mangrove stand varied significantly according to the season and mangrove zone. The overall results suggest that the Praia Salgada mangrove stand provides a nursery function for several of the studied fish species.

Towards risk assessment for antibiotic resistant pathogens in recycled water: a systematic review and summary of research needs - Emily Garner; Marisa Organiscak; Lucien Dieter; Carley Shingleton; Madison Haddix; Sayalee Joshi; Amy Pruden; Nicholas J. Ashbolt; Gertjan Medema; Kerry A. Hamilton (Environmental Microbiology, 2021)
Summary Risk assessment is critical for identifying target concentrations of antibiotic resistant pathogens necessary for mitigating potential harmful exposures associated with water reuse. However, there is currently limited available data characterizing the concentrations of antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in recycled water to support robust efforts at risk assessment. The objective of this systematic review was to identify and synthesize the existing literature documenting the presence and abundance of ARB and ARGs in recycled water. In addition, this review identifies best practices and explores monitoring targets for studying ARB and ARGs in recycled water to guide future work and identifies key research needs aimed at better supporting quantitative microbial risk assessment focused on recycled water and antibiotic resistance. Future efforts to collect data about ARB and ARG prevalence in recycled water should report concentration data per unit volume. Sample metadata should also be provided, including a description of treatment approach, a description of planned water uses (e.g., potable, irrigation), methods for conveyance to the point of use, and available physicochemical water quality data. Additional research is needed aimed at identifying recommended ARB and ARG monitoring targets and for developing approaches to incorporate metagenomic data into risk assessment.

Prevalence and predictors of REM sleep without atonia in a sleep clinic population - C. Yu; J. Stonehouse; A. R. Turton; S. A. Joosten; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

Crop uptake of heavy metals in response to the environment and agronomic practices on land near mine tailings in the Zambian Copperbelt Province - Belinda Kaninga; R. Murray Lark; Benson H. Chishala; Kakoma K. Maseka; Godfrey M. Sakala; Scott D. Young; Andrew Tye; Elliott M. Hamilton; Michael J. Watts (Environmental Geochemistry and Health, 2021)

Angioplasty Induced Changes in Dialysis Vascular Access Compliance - Yihao Zheng; Brian J. Thelen; Nirmala Rajaram; Venkataramu N. Krishnamurthy; James Hamilton; Miguel Angel Funes-Lora; Timothy Morgan; Lenar Yessayan; Brandie Bishop; Nickolas Osborne; Peter Henke; Albert J. Shih; et al. (Annals of Biomedical Engineering, 2021)

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Examination of FERMT1 expression in placental chorionic villi and its role in HTR8-SVneo cell invasion - E. Kawamura; G. B. Hamilton; E. I. Miskiewicz; D. J. MacPhee (Histochemistry and Cell Biology, 2021)

Comprehensive genus-wide screening of seahorse microsatellite loci identifies priority species for conservation assessment - A. B. Wilson; J. Ashe; M. Padron; H. Hamilton (Conservation Genetics Resources, 2021)

A highly species-rich jaw-bone artefact from New Guinea - Andrew J. Hamilton; Bronwyn Hopwood (Archaeological and Anthropological Sciences, 2021)

Corrigendum to: The global Microcystis interactome - K.V. Cook; C. Li; H. Cai; L.R. Krumholz; K.D. Hambright; H.W. Paerl; M.M. Steffen; A.E. Wilson; M.A. Burford; H.‐P. Grossart; D. P. Hamilton; H. Jiang; et al. (Limnology and Oceanography, 2021)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Motor unit action potential amplitude during low torque fatiguing contractions versus high torque non-fatiguing contractions: a multilevel analysis - Kylie K. Harmon; Adam S. Hamilton; Brent D. Johnson; Frank J. Bartek; Ryan M. Girts; Rob J. MacLennan; Debbie L. Hahs-Vaughn; Matt S. Stock (European Journal of Applied Physiology, 2021)

Therapeutic treatment of dietary docosahexaenoic acid for particle-induced pulmonary inflammation in Balb/c mice - Paige Fletcher; Raymond F. Hamilton; Joseph F. Rhoderick; Britten Postma; Mary Buford; James J. Pestka; Andrij Holian (Inflammation Research, 2021)

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

Talin-dependent integrin activation is required for endothelial proliferation and postnatal angiogenesis - Fadi E. Pulous; Jamie C. Carnevale; Zaki Al-Yafeai; Brenna H. Pearson; Jamie A. G. Hamilton; Curtis J. Henry; A. Wayne Orr; Brian G. Petrich (Angiogenesis, 2021)

Dietary intake, eating behavior and physical activity in individuals with and without obstructive sleep apnea - Caroline J. Beatty; Shane A. Landry; Joy Lee; Simon A. Joosten; Anthony Turton; Denise M. O’Driscoll; Ai-Ming Wong; Luke Thomson; Bradley A. Edwards; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

Spatial analysis of urine zinc (Zn) concentration for women of reproductive age and school age children in Malawi - Felix P. Phiri; E. Louise Ander; R. Murray Lark; Edward J. M. Joy; Alexander A. Kalimbira; Parminder S. Suchdev; Jellita Gondwe; Elliott M. Hamilton; Michael J. Watts; Martin R. Broadley (Environmental Geochemistry and Health, 2021)
Zinc (Zn) is an essential micronutrient, and Zn deficiency remains a major global public health challenge. Recognised biomarkers of population Zn status include blood plasma or serum Zn concentration and proxy data such as dietary Zn intake and prevalence of stunting. Urine Zn concentration is rarely used to assess population Zn status. This study assessed the value of urine Zn concentration as a biomarker of population Zn status using a nationally representative sample of non-pregnant women of reproductive age (WRA) and school-aged children (SAC) in Malawi. Spot (casual) urine samples were collected from 741 WRA and 665 SAC. Urine Zn concentration was measured by inductively coupled plasma mass spectrometry with specific gravity adjustment for hydration status. Data were analysed using a linear mixed model with a spatially correlated random effect for between-cluster variation. The effect of time of sample collection (morning or afternoon), and gender (for SAC), on urine Zn concentration were examined. There was spatial dependence in urine Zn concentration between clusters among SAC but not WRA, which indicates that food system or environmental factors can influence urine Zn concentration. Mapping urine Zn concentration could potentially identify areas where the prevalence of Zn deficiency is greater and thus where further sampling or interventions might be targeted. There was no evidence for differences in urine Zn concentration between gender ( P = 0.69) or time of sample collection ( P = 0.85) in SAC. Urine Zn concentration was greater in afternoon samples for WRA ( P = 0.003). Relationships between urine Zn concentration, serum Zn concentration, dietary Zn intake, and potential food systems covariates warrant further study.

Semiautomatic morphometric analysis of skeletal muscle obtained by needle biopsy in older adults - Henry J. Bonilla; Maria L. Messi; Khalima A. Sadieva; Craig A. Hamilton; Aron S. Buchman; Osvaldo Delbono (GeroScience, 2020)

Geographic variation in responses of kelp forest communities of the California Current to recent climatic changes - Rodrigo Beas‐Luna; Fiorenza Micheli; C. Brock Woodson; Mark Carr; Dan Malone; Jorge Torre; Charles Boch; Jennifer E. Caselle; Matt Edwards; Jan Freiwald; Scott L. Hamilton; Arturo Hernandez; et al. (Global Change Biology, 2020)
The changing global climate is having profound effects on coastal marine ecosystems around the world. Structure, functioning, and resilience, however, can vary geographically, depending on species composition, local oceanographic forcing, and other pressures from human activities and use. Understanding ecological responses to environmental change and predicting changes in the structure and functioning of whole ecosystems require large‐scale, long‐term studies, yet most studies trade spatial extent for temporal duration. We address this shortfall by integrating multiple long‐term kelp forest monitoring datasets to evaluate biogeographic patterns and rates of change of key functional groups (FG) along the west coast of North America. Analysis of data from 469 sites spanning Alaska, USA, to Baja California, Mexico, and 373 species (assigned to 18 FG) reveals regional variation in responses to both long‐term (2006–2016) change and a recent marine heatwave (2014–2016) associated with two atmospheric and oceanographic anomalies, the “Blob” and extreme El Niño Southern Oscillation (ENSO). Canopy‐forming kelps appeared most sensitive to warming throughout their range. Other FGs varied in their responses among trophic levels, ecoregions, and in their sensitivity to heatwaves. Changes in community structure were most evident within the southern and northern California ecoregions, while communities in the center of the range were more resilient. We report a poleward shift in abundance of some key FGs. These results reveal major, ongoing region‐wide changes in productive coastal marine ecosystems in response to large‐scale climate variability, and the potential loss of foundation species. In particular, our results suggest that coastal communities that are dependent on kelp forests will be more impacted in the southern portion of the California Current region, highlighting the urgency of implementing adaptive strategies to sustain livelihoods and ensure food security. The results also highlight the value of multiregional integration and coordination of monitoring programs for improving our understanding of marine ecosystems, with the goal of informing policy and resource management in the future.

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Microbiota of Four Tissue Types in American Alligators (Alligator mississippiensis) Following Extended Dietary Selenomethionine Exposure - Troy J. Kieran; Samantha J. Goodman; John W. Finger; Jesse C. Thomas; Matthew T. Hamilton; Tracey D. Tuberville; Travis C. Glenn (Bulletin of Environmental Contamination and Toxicology, 2020)

Comparative landscape genetics reveals differential effects of environment on host and pathogen genetic structure in Tasmanian devils ( Sarcophilus harrisii ) and their transmissible tumour - Christopher P. Kozakiewicz; Lauren Ricci; Austin H. Patton; Amanda R. Stahlke; Sarah A. Hendricks; Mark J. Margres; Manuel Ruiz‐Aravena; David G. Hamilton; Rodrigo Hamede; Hamish McCallum; Menna E. Jones; Paul A. Hohenlohe; et al. (Molecular Ecology, 2020)
Genetic structure in host species is often used to predict disease spread. However, host and pathogen genetic variation may be incongruent. Understanding landscape factors that have either concordant or divergent influence on host and pathogen genetic structure is crucial for wildlife disease management. Devil facial tumour disease (DFTD) was first observed in 1996 and has spread throughout almost the entire Tasmanian devil geographic range, causing dramatic population declines. Whereas DFTD is predominantly spread via biting among adults, devils typically disperse as juveniles, which experience low DFTD prevalence. Thus, we predicted little association between devil and tumour population structure and that environmental factors influencing gene flow differ between devils and tumours. We employed a comparative landscape genetics framework to test the influence of environmental factors on patterns of isolation by resistance (IBR) and isolation by environment (IBE) in devils and DFTD. Although we found evidence for broad‐scale costructuring between devils and tumours, we found no relationship between host and tumour individual genetic distances. Further, the factors driving the spatial distribution of genetic variation differed for each. Devils exhibited a strong IBR pattern driven by major roads, with no evidence of IBE. By contrast, tumours showed little evidence for IBR and a weak IBE pattern with respect to elevation in one of two tumour clusters we identify herein. Our results warrant caution when inferring pathogen spread using host population genetic structure and suggest that reliance on environmental barriers to host connectivity may be ineffective for managing the spread of wildlife diseases. Our findings demonstrate the utility of comparative landscape genetics for identifying differential factors driving host dispersal and pathogen transmission.

Comparing the fate of brain metastatic breast cancer cells in different immune compromised mice with cellular magnetic resonance imaging - Natasha N. Knier; Amanda M. Hamilton; Paula J. Foster (Clinical & Experimental Metastasis, 2020)

Spatial variability of sediment methane production and methanogen communities within a eutrophic reservoir: Importance of organic matter source and quantity - Megan E. Berberich; Jake J. Beaulieu; Trinity L. Hamilton; Sarah Waldo; Ishi Buffam (Limnology and Oceanography, 2020)
Freshwater reservoirs are an important source of the greenhouse gas methane (CH 4 ) to the atmosphere, but global emission estimates are poorly constrained (13.3–52.5 Tg C yr −1 ), partially due to extreme spatial variability in emission rates within and among reservoirs. Spatial heterogeneity in the availability of organic matter (OM) for biological CH 4 production by methanogenic archaea may be an important contributor to this variation. To investigate this, we measured sediment CH 4 potential production rates, OM source and quantity, and methanogen community composition at 15 sites within a eutrophic reservoir in Ohio, USA. CH 4 production rates were highest in the shallow riverine inlet zone of the reservoir, even when rates were normalized to OM quantity, indicating that OM was more readily utilized by methanogens in the riverine zone than in the transitional or lacustrine zones. Sediment stable isotopes and C:N indicated a greater proportion of terrestrial OM in the particulate sediment of this zone. Methanogens were present at all sites, but the riverine zone contained a higher relative abundance of methanogens capable of acetoclastic and methylotrophic methanogenesis, likely reflecting differences in decomposition processes or OM quality. While we found that methane potential production rates were negatively correlated with autochthonous carbon in particulate sediment OM, rates were positively correlated with indicators of autochthonous carbon in the porewater dissolved OM. It is likely that both dissolved and particulate sediment OM affect CH 4 production rates, and that both terrestrial and aquatic OM sources are important in the riverine methane production hot spot.

Multiple axes of ecological vulnerability to climate change - Matthew M. Kling; Stephanie L. Auer; Patrick J. Comer; David D. Ackerly; Healy Hamilton (Global Change Biology, 2020)
Observed ecological responses to climate change are highly individualistic across species and locations, and understanding the drivers of this variability is essential for management and conservation efforts. While it is clear that differences in exposure, sensitivity, and adaptive capacity all contribute to heterogeneity in climate change vulnerability, predicting these features at macroecological scales remains a critical challenge. We explore multiple drivers of heterogeneous vulnerability across the distributions of 96 vegetation types of the ecologically diverse western US, using data on observed climate trends from 1948 to 2014 to highlight emerging patterns of change. We ask three novel questions about factors potentially shaping vulnerability across the region: (a) How does sensitivity to different climate variables vary geographically and across vegetation classes? (b) How do multivariate climate exposure patterns interact with these sensitivities to shape vulnerability patterns? (c) How different are these vulnerability patterns according to three widely implemented vulnerability paradigms—niche novelty (decline in modeled suitability), temporal novelty (standardized anomaly), and spatial novelty (inbound climate velocity)—each of which uses a distinct frame of reference to quantify climate departure? We propose that considering these three novelty paradigms in combination could help improve our understanding and prediction of heterogeneous climate change responses, and we discuss the distinct climate adaptation strategies connected with different combinations of high and low novelty across the three metrics. Our results reveal a diverse mosaic of climate change vulnerability signatures across the region's plant communities. Each of the above factors contributes strongly to this heterogeneity: climate variable sensitivity exhibits clear patterns across vegetation types, multivariate climate change data reveal highly diverse exposure signatures across locations, and the three novelty paradigms diverge widely in their climate change vulnerability predictions. Together, these results shed light on potential drivers of individualistic climate change responses and may help to inform effective management strategies.

Using human hair and nails as biomarkers to assess exposure of potentially harmful elements to populations living near mine waste dumps - Lukundo Nakaona; Kakoma K. Maseka; Elliott M. Hamilton; Michael J. Watts (Environmental Geochemistry and Health, 2020)

Iodine status in western Kenya: a community-based cross-sectional survey of urinary and drinking water iodine concentrations - Michael J. Watts; Daniel R. S. Middleton; Andrew Marriott; Olivier S. Humphrey; Elliott Hamilton; Valerie McCormack; Diana Menya; Jessica Farebrother; Odipo Osano (Environmental Geochemistry and Health, 2020)

Feral cat eradication on Dirk Hartog Island, Western Australia - D. Algar; M. Johnston; C. Tiller; M. Onus; J. Fletcher; G. Desmond; N. Hamilton; P. Speldewinde (Biological Invasions, 2020)

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Racial/ethnic differences in patient experiences with health care in association with earlier stage at breast cancer diagnosis: findings from the SEER-CAHPS data - Albert J. Farias; Carol Y. Ochoa; Gabriela Toledo; Soo-In Bang; Ann S. Hamilton; Xianglin L. Du (Cancer Causes & Control, 2020)

Prevalence and Genetic Diversity of Toxoplasma gondii in Free-Ranging Chickens from the Caribbean - C. M. Hamilton; R. Robins; R. Thomas; C. Oura; S. Oliveira; I. Villena; E. A. Innes; F. Katzer; P. J. Kelly (Acta Parasitologica, 2019)

The Antarctic mite, Alaskozetes antarcticus, shares bacterial microbiome community membership but not abundance between adults and tritonymphs - Christopher J. Holmes; Emily C. Jennings; J. D. Gantz; Drew Spacht; Austin A. Spangler; David L. Denlinger; Richard E. Lee; Trinity L. Hamilton; Joshua B. Benoit (Polar Biology, 2019)

Velocity Curvature Index: a Novel Diagnostic Biomarker for Large Vessel Occlusion - Samuel G. Thorpe; Corey M. Thibeault; Seth J. Wilk; Michael O’Brien; Nicolas Canac; Mina Ranjbaran; Christian Devlin; Thomas Devlin; Robert B. Hamilton (Translational Stroke Research, 2019)

Foraging consistency of coral reef fishes across environmental gradients in the central Pacific - Brian J. Zgliczynski; Gareth J. Williams; Scott L. Hamilton; Elisabeth G. Cordner; Michael D. Fox; Yoan Eynaud; Robert H. Michener; Les S. Kaufman; Stuart A. Sandin (Oecologia, 2019)

Iodine uptake, storage and translocation mechanisms in spinach (Spinacia oleracea L.) - O. S. Humphrey; S. D. Young; E. H. Bailey; N. M. J. Crout; E. L. Ander; E. M. Hamilton; M. J. Watts (Environmental Geochemistry and Health, 2019)

Male aggression varies with consortship rate and habitat in a dolphin social network - Rebecca A. Hamilton; Teresa Borcuch; Simon J. Allen; William R. Cioffi; Vanni Bucci; Michael Krützen; Richard C. Connor (Behavioral Ecology and Sociobiology, 2019)

A Quantitative Meta-analysis of Olfactory Dysfunction in Epilepsy - Kiran Khurshid; Andrew J. D. Crow; Petra E. Rupert; Nancy L. Minniti; Melissa A. Carswell; Dawn J. Mechanic-Hamilton; Vidyulata Kamath; Richard L. Doty; Paul J. Moberg; David R. Roalf (Neuropsychology Review, 2019)

The small-world topology of Clovis lithic networks - Briggs Buchanan; Marcus J. Hamilton; J. David Kilby (Archaeological and Anthropological Sciences, 2019)

Comparison of Unyvero P55 Pneumonia Cartridge, in-house PCR and culture for the identification of respiratory pathogens and antibiotic resistance in bronchoalveolar lavage fluids in the critical care setting - Naomi J. Gadsby; Martin P. McHugh; Callum Forbes; Laura MacKenzie; Stephen K. D. Hamilton; David M. Griffith; Kate E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Community-based management fails to halt declines of bumphead parrotfish and humphead wrasse in Roviana Lagoon, Solomon Islands - Richard J. Hamilton; Alec Hughes; Christopher J. Brown; Tingo Leve; Warren Kama (Coral Reefs, 2019)

A process of convergent amplification and tissue‐specific expression dominates the evolution of toxin and toxin‐like genes in sea anemones - Joachim M. Surm; Hayden L. Smith; Bruno Madio; Eivind A.B. Undheim; Glenn F. King; Brett R. Hamilton; Chloé A. van der Burg; Ana Pavasovic; Peter J. Prentis (Molecular Ecology, 2019)
Members of phylum Cnidaria are an ancient group of venomous animals and rely on a number of specialized tissues to produce toxins in order to fulfil a range of ecological roles including prey capture, defence against predators, digestion and aggressive encounters. However, limited comprehensive analyses of the evolution and expression of toxin genes currently exist for cnidarian species. In this study, we use genomic and transcriptomic sequencing data to examine gene copy number variation and selective pressure on toxin gene families in phylum Cnidaria. Additionally, we use quantitative RNA‐seq and mass spectrometry imaging to understand expression patterns and tissue localization of toxin production in sea anemones. Using genomic data, we demonstrate that the first large‐scale expansion and diversification of known toxin genes occurs in phylum Cnidaria, a process we also observe in other venomous lineages, which we refer to as convergent amplification. Our analyses of selective pressure on sea anemone toxin gene families reveal that purifying selection is the dominant mode of evolution for these genes and that phylogenetic inertia is an important determinant of toxin gene complement in this group. The gene expression and tissue localization data revealed that specific genes and proteins from toxin gene families show strong patterns of tissue and developmental‐phase specificity in sea anemones. Overall, convergent amplification and phylogenetic inertia have strongly influenced the distribution and evolution of the toxin complement observed in sea anemones, while the production of venoms with different compositions across tissues is related to the functional and ecological roles undertaken by each tissue type.

Characterization of Male-Produced Aggregation Pheromone of the Bean Flower Thrips Megalurothrips sjostedti (Thysanoptera: Thripidae) - Saliou Niassy; Amanuel Tamiru; James G. C. Hamilton; William D. J. Kirk; Roland Mumm; Cassie Sims; Willem Jan de Kogel; Sunday Ekesi; Nguya K. Maniania; Krishnakumari Bandi; Fraser Mitchell; Sevgan Subramanian (Journal of Chemical Ecology, 2019)

Integrated in vitro models for hepatic safety and metabolism: evaluation of a human Liver-Chip and liver spheroid - Alison J. Foster; Bhavik Chouhan; Sophie L. Regan; Helen Rollison; Sara Amberntsson; Linda C. Andersson; Abhishek Srivastava; Malin Darnell; Jonathan Cairns; Stanley E. Lazic; Kyung-Jin Jang; Debora B. Petropolis; et al. (Archives of Toxicology, 2019)

Investigating the scale of prehistoric social networks using culture, language, and point types in western North America - Briggs Buchanan; Marcus J. Hamilton; James C. Hartley; Steven L. Kuhn (Archaeological and Anthropological Sciences, 2019)

Resistance training in young men induces muscle transcriptome-wide changes associated with muscle structure and metabolism refining the response to exercise-induced stress - Felipe Damas; Carlos Ugrinowitsch; Cleiton A. Libardi; Paulo R. Jannig; Amy J. Hector; Chris McGlory; Manoel E. Lixandrão; Felipe C. Vechin; Horacio Montenegro; Valmor Tricoli; Hamilton Roschel; Stuart M. Phillips (European Journal of Applied Physiology, 2018)

The world’s largest parrotfish has slow growth and a complex reproductive ecology - Brett M. Taylor; Richard J. Hamilton; Glenn R. Almany; J. Howard Choat (Coral Reefs, 2018)

Geographic and temporal variations in turbulent heat loss from lakes: A global analysis across 45 lakes - R. Iestyn Woolway; Piet Verburg; John D. Lenters; Christopher J. Merchant; David P. Hamilton; Justin Brookes; Elvira de Eyto; Sean Kelly; Nathan C. Healey; Simon Hook; Alo Laas; Don Pierson; et al. (Limnology and Oceanography, 2018)
Heat fluxes at the lake surface play an integral part in determining the energy budget and thermal structure in lakes, including regulating how lakes respond to climate change. We explore patterns in turbulent heat fluxes, which vary across temporal and spatial scales, using in situ high‐frequency monitoring data from 45 globally distributed lakes. Our analysis demonstrates that some of the lakes studied follow a marked seasonal cycle in their turbulent surface fluxes and that turbulent heat loss is highest in larger lakes and those situated at low latitude. The Bowen ratio, which is the ratio of mean sensible to mean latent heat fluxes, is smaller at low latitudes and, in turn, the relative contribution of evaporative to total turbulent heat loss increases toward the tropics. Latent heat transfer ranged from ~ 60% to > 90% of total turbulent heat loss in the examined lakes. The Bowen ratio ranged from 0.04 to 0.69 and correlated significantly with latitude. The relative contributions to total turbulent heat loss therefore differ among lakes, and these contributions are influenced greatly by lake location. Our findings have implications for understanding the role of lakes in the climate system, effects on the lake water balance, and temperature‐dependent processes in lakes.

From Gondwana to GAAR landia: Evolutionary history and biogeography of ogre‐faced spiders ( Deinopis ) - Lisa Chamberland; Anne McHugh; Sarah Kechejian; Greta J. Binford; Jason E. Bond; Jonathan Coddington; Gaynor Dolman; Chris A. Hamilton; Mark S. Harvey; Matjaž Kuntner; Ingi Agnarsson (Journal of Biogeography, 2018)
Aim We explore the evolutionary history of the ogre‐faced spiders ( Deinopis ) from their Early Cretaceous origins to present day. Specifically, we investigate how vicariance and dispersal have shaped distribution patterns of this lineage. Within the Caribbean, we test the role of GAAR landia, a hypothesized land bridge that connected South America to the Greater Antilles during the Eocene–Oligocene transition (~35–33 Ma), in the biogeography of Deinopis . Taxon Araneae: Deinopidae: Deinopis . Location Caribbean islands, with additional global exemplars. Methods Combining standard Sanger sequence data with an Anchored Hybrid Enrichment ( AHE ) phylogenomic dataset, we use Bayesian inference to estimate the phylogenetic relationships of Deinopis . “BioGeo BEARS ” is used to test the GAAR landia hypothesis, and to pinpoint major dispersal events in the biogeographic history of Deinopis . Results The phylogeny supports the nesting of a Caribbean clade within a continental grade. Model comparisons indicate GAAR landia as the best fitting model, and the biogeographic analyses reflect the geologic history within the Caribbean. Ancient and recent overwater dispersal events are also indicated within this lineage. There is also an ancient 113 Ma split into Old and New World clades. Main Conclusions The Deinopis phylogeny corresponds well with geography. This is reflected in the support for the GAAR landia land bridge hypothesis and the phylogenetic relationships within and among Caribbean islands mirroring nuances of Caribbean geologic history. Overwater dispersal also plays an important role in the biogeographic history of this lineage as implicated in the colonization of the volcanic and sedimentary Lesser Antilles and in a “reverse” colonization of North America. The spider family Deinopidae is an ancient lineage with origins dating back to Gondwana. While overwater dispersal has clearly played a role in the biogeography of the genus, the Deinopis phylogeny bears a strong signature of ancient geological events.

Establishment of the exotic invasive Cuban treefrog (Osteopilus septentrionalis) in Louisiana - Brad M. Glorioso; James Hardin Waddle; Lindy J. Muse; Nicole D. Jennings; Melanie Litton; Joel Hamilton; Steven Gergen; David Heckard (Biological Invasions, 2018)

The effect of ammonia on canine polymorphonuclear cells - Craig R. Breheny; Richard J. Mellanby; Julie A. Hamilton; Adam G. Gow (Veterinary Research Communications, 2018)

Estimating the footprint of pollution on coral reefs with models of species turnover - Christopher J. Brown; Richard J. Hamilton (Conservation Biology, 2018)
Ecological communities typically change along gradients of human impact, although it is difficult to estimate the footprint of impacts for diffuse threats such as pollution. We developed a joint model (i.e., one that includes multiple species and their interactions with each other and environmental covariates) of benthic habitats on lagoonal coral reefs and used it to infer change in benthic composition along a gradient of distance from logging operations. The model estimated both changes in abundances of benthic groups and their compositional turnover, a type of beta diversity. We used the model to predict the footprint of turbidity impacts from past and recent logging. Benthic communities far from logging were dominated by branching corals, whereas communities close to logging had higher cover of dead coral, massive corals, and soft sediment. Recent impacts were predicted to be small relative to the extensive impacts of past logging because recent logging has occurred far from lagoonal reefs. Our model can be used more generally to estimate the footprint of human impacts on ecosystems and evaluate the benefits of conservation actions for ecosystems.

Methane variability associated with natural and anthropogenic sources in an Australian context - M. A. Hatch; M. J. Kennedy; M. W. Hamilton; R. A. Vincent (Australian Journal of Earth Sciences, 2018)

Information and support needs of young women regarding breast cancer risk and genetic testing: adapting effective interventions for a novel population - Suzanne C. O’Neill; Chalanda Evans; Rebekah J. Hamilton; Beth N. Peshkin; Claudine Isaacs; Sue Friedman; Kenneth P. Tercyak (Familial Cancer, 2018)

Interaction of preservation methods and radiation sterilization in human skin processing, with particular insight on the impact of the final water content and collagen disruption. Part I: process validation, water activity and collagen changes in tissues cryopreserved or processed using 50, 85 or 98% glycerol solutions - M. R. Herson; K. Hamilton; J. White; D. Alexander; S. Poniatowski; A. J. O’Connor; J. A. Werkmeister (Cell and Tissue Banking, 2018)

Global species delimitation and phylogeography of the circumtropical ‘sexy shrimp’ Thor amboinensis reveals a cryptic species complex and secondary contact in the Indo‐West Pacific - Benjamin M. Titus; Marymegan Daly; Natalie Hamilton; Michael L. Berumen; J. Antonio Baeza (Journal of Biogeography, 2018)
Aim The “sexy shrimp” Thor amboinensis is currently considered a single circumtropical species. However, the tropical oceans are partitioned by hard and soft barriers to dispersal, providing ample opportunity for allopatric speciation. Herein, we test the null hypothesis that T. amboinensis is a single global species, reconstruct its global biogeographical history, and comment on population‐level patterns throughout the Tropical Western Atlantic. Location Coral reefs in all tropical oceans. Methods Specimens of Thor amboinensis were obtained through field collection and museum holdings. We used one mitochondrial ( COI ) and two nuclear (NaK, enolase) gene fragments for global species delimitation and phylogenetic analyses ( n = 83 individuals, 30 sample localities), while phylogeographical reconstruction in the TWA was based on COI only ( n = 303 individuals, 10 sample localities). Results We found evidence for at least five cryptic lineages (9%–22% COI pairwise sequence divergence): four in the Indo‐West Pacific and one in the Tropical Western Atlantic. Phylogenetic reconstruction revealed that endemic lineages from Japan and the South Central Pacific are more closely related to the Tropical Western Atlantic lineage than to a co‐occurring lineage that is widespread throughout the Indo‐West Pacific. Concatenated and species tree phylogenetic analyses differ in the placement of an endemic Red Sea lineage and suggest alternate dispersal pathways into the Atlantic. Phylogeographical reconstruction throughout the Tropical Western Atlantic reveals little genetic structure over more than 3,000 km. Main conclusions Thor amboinensis is a species complex that has undergone a series of allopatric speciation events and whose members are in secondary contact in the Indo‐West Pacific. Nuclear‐ and mitochondrial‐ gene phylogenies show evidence of introgression between lineages inferred to have been separated more than 20 Ma. Phylogenetic discordance between multi‐locus analyses suggest that T. amboinensis originated in the Tethys sea and dispersed into the Atlantic and Indo‐West Pacific through the Tethys seaway or, alternatively, originated in the Indo‐West Pacific and dispersed into the Atlantic around South Africa. Population‐level patterns in the Caribbean indicate extensive gene flow across the region.

Outbreaks of Legionnaires’ Disease and Pontiac Fever 2006–2017 - K. A. Hamilton; A. J. Prussin; W. Ahmed; C. N. Haas (Current Environmental Health Reports, 2018)

Computation of the inverse additive relationship matrix for autopolyploid and multiple-ploidy populations - Matthew G. Hamilton; Richard J. Kerr (Theoretical and Applied Genetics, 2018)

Perineuronal nets labeled by monoclonal antibody VC1.1 ensheath interneurons expressing parvalbumin and calbindin in the rat amygdala - Alexander J. McDonald; Patricia G. Hamilton; Colin J. Barnstable (Brain Structure and Function, 2018)

Re-evaluating conservation priorities of New World tarantulas (Araneae: Theraphosidae) in a molecular framework indicates non-monophyly of the genera, Aphonopelma and Brachypelma - Steven P. Turner; Stuart J. Longhorn; Chris A. Hamilton; Ray Gabriel; Fernando PÉrez-Miles; Alfried P. Vogler (Systematics and Biodiversity, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Effects of Long-Term Anthropogenic Disturbance on the Benthic Episammic Diatom Community of an Ancient, Tropical Lake - Andrew J. Bramburger; Paul B. Hamilton; G. Douglas Haffner (Bulletin of Environmental Contamination and Toxicology, 2017)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Elemental composition of Malawian rice - Edward J. M. Joy; E. Louise Ander; Martin R. Broadley; Scott D. Young; Allan D. C. Chilimba; Elliott M. Hamilton; Michael J. Watts (Environmental Geochemistry and Health, 2017)

Isotopically (δ13C and δ18O) heavy volcanic plumes from Central Andean volcanoes: a field study - C. Ian Schipper; Yves Moussallam; Aaron Curtis; Nial Peters; Talfan Barnie; Philipson Bani; H. J. Jost; Doug Hamilton; Alessandro Aiuppa; Giancarlo Tamburello; Gaetano Giudice (Bulletin of Volcanology, 2017)

Syrian hamster neuroplasticity mechanisms fail as temperature declines to 15 °C, but histaminergic neuromodulation persists - Jock S. Hamilton; Sat M. Chau; Kevin J. Malins; Giancarlo G. Ibanez; John M. Horowitz; Barbara A. Horwitz (Journal of Comparative Physiology B, 2017)

Short-Term Response of a Downstream Marine System to the Partial Opening of a Tidal-River Causeway - Travis G. Gerwing; Diana J. Hamilton; Myriam A. Barbeau; Katy Haralampides; Gordon Yamazaki (Estuaries and Coasts, 2017)

Influence of Nrf2 activators on subcellular skeletal muscle protein and DNA synthesis rates after 6 weeks of milk protein feeding in older adults - Adam R. Konopka; Jaime L. Laurin; Robert V. Musci; Christopher A. Wolff; Justin J. Reid; Laurie M. Biela; Qian Zhang; Fredrick F. Peelor; Christopher L. Melby; Karyn L. Hamilton; Benjamin F. Miller (GeroScience, 2017)

Effect of water on the fluorine and chlorine partitioning behavior between olivine and silicate melt - Bastian Joachim; André Stechern; Thomas Ludwig; Jürgen Konzett; Alison Pawley; Lorraine Ruzié-Hamilton; Patricia L. Clay; Ray Burgess; Christopher J. Ballentine (Contributions to Mineralogy and Petrology, 2017)

Schema vs. primitive perceptual grouping: the relative weighting of sequential vs. spatial cues during an auditory grouping task in frogs - Hamilton E. Farris; Michael J. Ryan (Journal of Comparative Physiology A, 2017)

Aerosols in the Pre-industrial Atmosphere - Kenneth S. Carslaw; Hamish Gordon; Douglas S. Hamilton; Jill S. Johnson; Leighton A. Regayre; M. Yoshioka; Kirsty J. Pringle (Current Climate Change Reports, 2017)

In vivo magnetic resonance imaging investigating the development of experimental brain metastases due to triple negative breast cancer - Amanda M. Hamilton; Paula J. Foster (Clinical & Experimental Metastasis, 2017)

Variability in the chemistry of private drinking water supplies and the impact of domestic treatment systems on water quality - E. L. Ander; M. J. Watts; P. L. Smedley; E. M. Hamilton; R. Close; H. Crabbe; T. Fletcher; A. Rimell; M. Studden; G. Leonardi (Environmental Geochemistry and Health, 2016)

Hyperstability masks declines in bumphead parrotfish (Bolbometopon muricatum) populations - Richard J. Hamilton; Glenn R. Almany; Don Stevens; Michael Bode; John Pita; Nate A. Peterson; J. Howard Choat (Coral Reefs, 2016)

Periostin as a multifunctional modulator of the wound healing response - John T. Walker; Karrington McLeod; Shawna Kim; Simon J. Conway; Douglas W. Hamilton (Cell and Tissue Research, 2016)

Wildfire, climate, and perceptions in Northeast Oregon - Lawrence C. Hamilton; Joel Hartter; Barry D. Keim; Angela E. Boag; Michael W. Palace; Forrest R. Stevens; Mark J. Ducey (Regional Environmental Change, 2016)

Wind forced circulation and sediment disturbance in a temperate lake - M Gibbs; J Abell; D Hamilton (New Zealand Journal of Marine and Freshwater Research, 2016)
Meteorological forcing on the surface of a lake can generate mixing and transport processes that alter water quality. This study examined how meteorological forcing affected water currents in Lake Rotorua—a large, shallow, temperate, polymictic lake—during a period of sustained vertical mixing and strong winds. Acoustic Doppler current profiler (ADCP) measurements were recorded at two sites and a hydrodynamic model (ELCOM) was used to simulate water movement over the period of ADCP measurements. Model simulations show circulation patterns in Lake Rotorua are strongly influenced by the topography of the lake and, to a lesser extent, the catchment, with little variation in currents with depth during winter mixing. Northeasterly winds produced a clockwise circulation around the mid‐lake island with a second anticlockwise gyre between the island and the western shore. This circulation pattern is consistent with topographic gyres found in other large lakes. A shift to a weaker southwesterly wind caused these circulation patterns to reverse direction over a period of c. 6 h, with a weak secondary gyre also occurring within the main anticlockwise circulation. The effect of this circulation pattern on the resuspension of sediment and thus potential in‐lake phosphorus control strategies is considered.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

The influence of status and the social environment on energy stores in a social fish - J. K. Hellmann; I. Y. Ligocki; C. M. O'Connor; A. R. Reddon; T. M. Farmer; S. E. Marsh‐Rollo; S. Balshine; I. M. Hamilton (Journal of Fish Biology, 2016)
This study explores how muscle and liver energy stores are linked with social status and the social environment in Neolamprologus pulcher , a cooperatively breeding fish that lives in colonies comprised of up to 200 distinct social groups. Subordinate muscle energy stores were positively correlated with the number of neighbouring social groups in the colony, but this pattern was not observed in dominant N. pulcher . Furthermore, liver energy stores were smaller in dominants living at the edge of the colony compared with those living in the colony centre, with no differences among subordinates in liver energy stores. Subordinate N. pulcher may build up large energy stores in the muscles to fuel rapid growth after dispersal, which could occur more frequently in high‐density environments. Dominant N. pulcher may use the more easily mobilized energy stores in the liver to fuel daily activities, which could be more energetically demanding on the edge of the colony as a result of the increased predation defence needed on the edge. Overall, this study demonstrates that both subordinate and dominant physiology in N. pulcher varies with characteristics of the social environment. Furthermore, dominant and subordinate energy storage strategies appear to differ due to status‐dependent variation in daily activities and variation in the need to prepare for future reproductive or dispersal opportunities.

The role of defensive ecological interactions in the evolution of conotoxins - J. R. Prashanth; S. Dutertre; A. H. Jin; V. Lavergne; B. Hamilton; F. C. Cardoso; J. Griffin; D. J. Venter; P. F. Alewood; R. J. Lewis (Molecular Ecology, 2016)
Venoms comprise of complex mixtures of peptides evolved for predation and defensive purposes. Remarkably, some carnivorous cone snails can inject two distinct venoms in response to predatory or defensive stimuli, providing a unique opportunity to study separately how different ecological pressures contribute to toxin diversification. Here, we report the extraordinary defensive strategy of the Rhizoconus subgenus of cone snails. The defensive venom from this worm‐hunting subgenus is unusually simple, almost exclusively composed of αD‐conotoxins instead of the ubiquitous αA‐conotoxins found in the more complex defensive venom of mollusc‐ and fish‐hunting cone snails. A similarly compartmentalized venom gland as those observed in the other dietary groups facilitates the deployment of this defensive venom. Transcriptomic analysis of a Conus vexillum venom gland revealed the αD‐conotoxins as the major transcripts, with lower amounts of 15 known and four new conotoxin superfamilies also detected with likely roles in prey capture. Our phylogenetic and molecular evolution analysis of the αD‐conotoxins from five subgenera of cone snails suggests they evolved episodically as part of a defensive strategy in the Rhizoconus subgenus. Thus, our results demonstrate an important role for defence in the evolution of conotoxins.

Isolation and characterization of 29 microsatellite markers for the bumphead parrotfish, Bolbometopon muricatum, and cross amplification in 12 related species - Mark A. Priest; Glenn R. Almany; Camrin D. Braun; Richard J. Hamilton; Diego F. Lozano-Cortés; Pablo Saenz-Agudelo; Michael L. Berumen (Marine Biodiversity, 2015)

Transatlantic secondary contact in Atlantic Salmon, comparing microsatellites, a single nucleotide polymorphism array and restriction‐site associated DNA sequencing for the resolution of complex spatial structure - Ian R. Bradbury; Lorraine C. Hamilton; Brian Dempson; Martha J. Robertson; Vincent Bourret; Louis Bernatchez; Eric Verspoor (Molecular Ecology, 2015)
Identification of discrete and unique assemblages of individuals or populations is central to the management of exploited species. Advances in population genomics provide new opportunities for re‐evaluating existing conservation units but comparisons among approaches remain rare. We compare the utility of RAD ‐seq, a single nucleotide polymorphism ( SNP ) array and a microsatellite panel to resolve spatial structuring under a scenario of possible trans‐Atlantic secondary contact in a threatened Atlantic Salmon, Salmo salar , population in southern Newfoundland. Bayesian clustering indentified two large groups subdividing the existing conservation unit and multivariate analyses indicated significant similarity in spatial structuring among the three data sets. mt DNA alleles diagnostic for European ancestry displayed increased frequency in southeastern Newfoundland and were correlated with spatial structure in all marker types. Evidence consistent with introgression among these two groups was present in both SNP data sets but not the microsatellite data. Asymmetry in the degree of introgression was also apparent in SNP data sets with evidence of gene flow towards the east or European type. This work highlights the utility of RAD ‐seq based approaches for the resolution of complex spatial patterns, resolves a region of trans‐Atlantic secondary contact in Atlantic Salmon in Newfoundland and demonstrates the utility of multiple marker comparisons in identifying dynamics of introgression.

Nanoparticles coated with the tumor-penetrating peptide iRGD reduce experimental breast cancer metastasis in the brain - Amanda M. Hamilton; Sallouha Aidoudi-Ahmed; Shweta Sharma; Venkata R. Kotamraju; Paula J. Foster; Kazuki N. Sugahara; Erkki Ruoslahti; Brian K. Rutt (Journal of Molecular Medicine, 2015)

Western Juniper Management: Assessing Strategies for Improving Greater Sage-grouse Habitat and Rangeland Productivity - Shahla Farzan; Derek J. N. Young; Allison G. Dedrick; Matthew Hamilton; Erik C. Porse; Peter S. Coates; Gabriel Sampson (Environmental Management, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Ten ways remote sensing can contribute to conservation - Robert A. Rose; Dirck Byler; J. Ron Eastman; Erica Fleishman; Gary Geller; Scott Goetz; Liane Guild; Healy Hamilton; Matt Hansen; Rachel Headley; Jennifer Hewson; Ned Horning; et al. (Conservation Biology, 2015)
In an effort to increase conservation effectiveness through the use of Earth observation technologies, a group of remote sensing scientists affiliated with government and academic institutions and conservation organizations identified 10 questions in conservation for which the potential to be answered would be greatly increased by use of remotely sensed data and analyses of those data. Our goals were to increase conservation practitioners’ use of remote sensing to support their work, increase collaboration between the conservation science and remote sensing communities, identify and develop new and innovative uses of remote sensing for advancing conservation science, provide guidance to space agencies on how future satellite missions can support conservation science, and generate support from the public and private sector in the use of remote sensing data to address the 10 conservation questions. We identified a broad initial list of questions on the basis of an email chain‐referral survey. We then used a workshop‐based iterative and collaborative approach to whittle the list down to these final questions (which represent 10 major themes in conservation): How can global Earth observation data be used to model species distributions and abundances? How can remote sensing improve the understanding of animal movements? How can remotely sensed ecosystem variables be used to understand, monitor, and predict ecosystem response and resilience to multiple stressors? How can remote sensing be used to monitor the effects of climate on ecosystems? How can near real‐time ecosystem monitoring catalyze threat reduction, governance and regulation compliance, and resource management decisions? How can remote sensing inform configuration of protected area networks at spatial extents relevant to populations of target species and ecosystem services? How can remote sensing‐derived products be used to value and monitor changes in ecosystem services? How can remote sensing be used to monitor and evaluate the effectiveness of conservation efforts? How does the expansion and intensification of agriculture and aquaculture alter ecosystems and the services they provide? How can remote sensing be used to determine the degree to which ecosystems are being disturbed or degraded and the effects of these changes on species and ecosystem functions?

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

Organic matter stocks increase with degree of invasion in temperate inland wetlands - J. P. Martina; S. K. Hamilton; M. R. Turetsky; C. J. Phillippo (Plant and Soil, 2014)

Stratigraphic and depositional framework of the Walloon Subgroup, eastern Surat Basin, Queensland - S. K. Hamilton; J. S. Esterle; R. Sliwa (Australian Journal of Earth Sciences, 2014)

Effects of a simulated upwelling event on the littoral epilithic diatom community of an ancient tropical lake (Lake Matano, Sulawesi Island, Indonesia) - Andrew J. Bramburger; Paul B. Hamilton; G. Douglas Haffner (Hydrobiologia, 2014)

Characterization of a thermophilic bacteriophage of Geobacillus kaustophilus - Timothy J. Marks; Paul T. Hamilton (Archives of Virology, 2014)

How much does a swimming, underweight, entangled right whale ( Eubalaena glacialis ) weigh? Calculating the weight at sea, to facilitate accurate dosing of sedatives to enable disentanglement - Ashley Barratclough; Paul D. Jepson; Philip K. Hamilton; Carolyn A. Miller; Kenady Wilson; Michael J. Moore (Marine Mammal Science, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Field comparison and crop production modeling of sweet corn and silage maize (Zea mays L.) with treated urban wastewater and freshwater - Hoi-Fei Mok; Kithsiri Bandara Dassanayake; Graham Hepworth; Andrew J. Hamilton (Irrigation Science, 2014)

The diet of M yotis lucifugus across C anada: assessing foraging quality and diet variability - Elizabeth L. Clare; William O. C. Symondson; Hugh Broders; François Fabianek; Erin E. Fraser; Alistair MacKenzie; Andrew Boughen; Rachel Hamilton; Craig K. R. Willis; Felix Martinez‐Nuñez; Allyson K. Menzies; Kaleigh J. O. Norquay; et al. (Molecular Ecology, 2014)
Variation in prey resources influences the diet and behaviour of predators. When prey become limiting, predators may travel farther to find preferred food or adjust to existing local resources. When predators are habitat limited, local resource abundance impacts foraging success. We analysed the diet of Myotis lucifugus (little brown bats) from Nova Scotia (eastern Canada) to the Northwest Territories (north‐western Canada). This distribution includes extremes of season length and temperature and encompasses colonies on rural monoculture farms, and in urban and unmodified areas. We recognized nearly 600 distinct species of prey, of which ≈30% could be identified using reference sequence libraries. We found a higher than expected use of lepidopterans, which comprised a range of dietary richness from ≈35% early in the summer to ≈55% by late summer. Diptera were the second largest prey group consumed, representing ≈45% of dietary diversity early in the summer. We observed extreme local dietary variability and variation among seasons and years. Based on the species of insects that were consumed, we observed that two locations support prey species with extremely low pollution and acidification tolerances, suggesting that these are areas without environmental contamination. We conclude that there is significant local population variability in little brown bat diet that is likely driven by seasonal and geographical changes in insect diversity, and that this prey may be a good indicator of environment quality.

Spatial and temporal patterns of carbon flow in a temperate, large river food web - Michael A. Pingram; Kevin J. Collier; David P. Hamilton; Brendan J. Hicks; Bruno O. David (Hydrobiologia, 2014)

Effects of flow on lateral interactions of fish and shrimps with off-channel habitats in a large river-floodplain system - K. Górski; K. J. Collier; D. P. Hamilton; B. J. Hicks (Hydrobiologia, 2014)

Impacts of pesticides in a Central California estuary - Brian Anderson; Bryn Phillips; John Hunt; Katie Siegler; Jennifer Voorhees; Kelly Smalling; Kathy Kuivila; Mary Hamilton; J. Ananda Ranasinghe; Ron Tjeerdema (Environmental Monitoring and Assessment, 2014)

Transcriptional responses in a D rosophila defensive symbiosis - Phineas T. Hamilton; Jong S. Leong; Ben F. Koop; Steve J. Perlman (Molecular Ecology, 2014)
Inherited symbionts are ubiquitous in insects and can have important consequences for the fitness of their hosts. Many inherited symbionts defend their hosts against parasites or other natural enemies; however, the means by which most symbionts confer protection is virtually unknown. We examine the mechanisms of defence in a recently discovered case of symbiont‐mediated protection, where the bacterial symbiont S piroplasma defends the fly D rosophila neotestacea from a virulent nematode parasite, H owardula aoronymphium . Using quantitative PCR of S piroplasma infection intensities and whole transcriptome sequencing, we attempt to distinguish between the following modes of defence: symbiont–parasite competition, host immune priming and the production of toxic factors by S piroplasma . Our findings do not support a model of exploitative competition between H owardula and S piroplasma to mediate defence, nor do we find strong support for host immune priming during S piroplasma infection. Interestingly, we recovered sequence for putative toxins encoded by S piroplasma , including a novel putative ribosome‐inactivating protein, transcripts of which are up‐regulated in response to nematode exposure. Protection via the production of toxins may be a widely used and important mechanism in heritable defensive symbioses in insects.

A framework for testing the ability of models to project climate change and its impacts - J. C. Refsgaard; H. Madsen; V. Andréassian; K. Arnbjerg-Nielsen; T. A. Davidson; M. Drews; D. P. Hamilton; E. Jeppesen; E. Kjellström; J. E. Olesen; T. O. Sonnenborg; D. Trolle; et al. (Climatic Change, 2014)

Software platforms to facilitate reconstructing genome‐scale metabolic networks - Joshua J. Hamilton; Jennifer L. Reed (Environmental Microbiology, 2014)
Summary System‐level analyses of microbial metabolism are facilitated by genome‐scale reconstructions of microbial biochemical networks. A reconstruction provides a structured representation of the biochemical transformations occurring within an organism, as well as the genes necessary to carry out these transformations, as determined by the annotated genome sequence and experimental data. Network reconstructions also serve as platforms for constraint‐based computational techniques, which facilitate biological studies in a variety of applications, including evaluation of network properties, metabolic engineering and drug discovery. Bottom‐up metabolic network reconstructions have been developed for dozens of organisms, but until recently, the pace of reconstruction has failed to keep up with advances in genome sequencing. To address this problem, a number of software platforms have been developed to automate parts of the reconstruction process, thereby alleviating much of the manual effort previously required. Here, we review four such platforms in the context of established guidelines for network reconstruction. While many steps of the reconstruction process have been successfully automated, some manual evaluation of the results is still required to ensure a high‐quality reconstruction. Widespread adoption of these platforms by the scientific community is underway and will be further enabled by exchangeable formats across platforms.

Feasibility and potential role of ferumoxytol-enhanced neuroimaging in HIV-associated neurocognitive disorder - Beau K. Nakamoto; Cecilia M. Shikuma; Debra Ogata-Arakaki; Tracie Umaki; Edward A. Neuwelt; Bruce T. Shiramizu; Dominic C. Chow; Nisha I. Parikh; Kalpana J. Kallianpur; Bronwyn E. Hamilton (Journal of NeuroVirology, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Impact of Eating Probiotic Yogurt on Colonization by Candida Species of the Oral and Vaginal Mucosa in HIV-Infected and HIV-Uninfected Women - Haihong Hu; Daniel J. Merenstein; Cuiwei Wang; Pilar R. Hamilton; Mandy L. Blackmon; Hui Chen; Richard A. Calderone; Dongmei Li (Mycopathologia, 2013)

Holocene paleoecology of a wild rice (Zizania sp.) lake in Northwestern Ontario, Canada - M. Boyd; C. Surette; J. Surette; I. Therriault; S. Hamilton (Journal of Paleolimnology, 2013)

Waterbird use of artificial wetlands in an Australian urban landscape - Christopher G. Murray; Sabine Kasel; Richard H. Loyn; Graham Hepworth; Andrew J. Hamilton (Hydrobiologia, 2013)

Influence of Intra- and Interspecific Interactions on Short-term Movement of the Amphipod Corophium volutator in Varying Environmental Conditions - David Drolet; Michael R. S. Coffin; Myriam A. Barbeau; Diana J. Hamilton (Estuaries and Coasts, 2013)

Central venous catheter-related blood stream infections in patients receiving intravenous iloprost for pulmonary hypertension - D. Sammut; C. A. Elliot; D. G. Kiely; I. J. Armstrong; L. Martin; J. Wilkinson; P. Sephton; J. Jones; N. Hamilton; J. Hurdman; E. McLellan; I. Sabroe; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Quantifying the production of dissolved organic nitrogen in headwater streams using 15 N tracer additions - Laura T. Johnson; Jennifer L. Tank; Robert O. Hall, Jr.; Patrick J. Mulholland; Stephen K. Hamilton; H. Maurice Valett; Jackson R. Webster; Melody J. Bernot; William H. McDowell; Bruce J. Peterson; Suzanne M. Thomas (Limnology and Oceanography, 2013)
Most nitrogen (N) assimilation in lake and marine ecosystems is often subsequently released via autochthonous dissolved organic nitrogen (DON) production, but autochthonous DON production has yet to be quantified in flowing waters. We measured in‐stream DON production following 24 h 15 N‐nitrate () tracer additions in 36 headwater streams, a subset of sites from the second Lotic Intersite Nitrogen eXperiment. Streams were located in five North American ecoregions and drained basins dominated by native vegetation, agriculture, or urban land use. Using a two‐compartment model, we could quantify DON production in 15 streams as a function of DO 15 N derived from 15 N tracer in biomass compartments. The streams with detectable DON production had higher % modified land use (agriculture + urban) in their basins than did streams with undetectable DON production. Median DON production represented 8% of total uptake when we used N biomass estimates based on N assimilated over 1 d (measured directly from the 15 N additions). Median DON production was 17% of total uptake when we used N assimilated over 42 d (extrapolated from previous 15 N tracer studies). Variation in DON production was positively correlated with ecosystem respiration, indicating that stream heterotrophy may influence DON production. In‐stream DON production was similar in magnitude to stream denitrification and nitrification, indicating that the production of autochthonous DON can represent a substantial transformation of stream N. Our results confirm that headwater streams can quickly convert inorganic N into organic forms, although the ultimate fate of DON remains unclear.

Comparative phylogeography of invasive Rattus rattus and Rattus norvegicus in the U.S. reveals distinct colonization histories and dispersal - Justin B. Lack; Meredith J. Hamilton; Janet K. Braun; Michael A. Mares; Ronald A. Van Den Bussche (Biological Invasions, 2013)

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Dynamics of the continent‐wide spread of a Drosophila defensive symbiont - Sarah N. Cockburn; Tamara S. Haselkorn; Phineas T. Hamilton; Elizabeth Landzberg; John Jaenike; Steve J. Perlman (Ecology Letters, 2013)
Facultative symbionts can represent important sources of adaptation for their insect hosts and thus have the potential for rapid spread. Drosophila neotestacea harbours a heritable symbiont, Spiroplasma , that confers protection against parasitic nematodes. We previously found a cline in Spiroplasma prevalence across central Canada, ending abruptly at the Rocky Mountains. Resampling these populations 9 years later revealed that Spiroplasma had increased substantially across the region, resembling a Fisherian wave of advance. Associations between Spiroplasma infection and host mitochondrial DNA indicate that the increase was due to local increase of Spiroplasma ‐infected flies. Finally, we detected Spiroplasma west of the Rocky Mountains for the first time and showed that defence against nematodes occurs in flies with a western genetic background. Because nematode infection is common throughout D. neotestacea 's range, we expect Spiroplasma to spread to the Pacific coast.

The life and times of ACC oxidase, alias TOM13 - Donald Grierson; Andrew J. Hamilton; Grantley W. Lycett (Molecular Biology Reports, 2013)

Do frog-eating bats perceptually bind the complex components of frog calls? - Patricia L. Jones; Hamilton E. Farris; Michael J. Ryan; Rachel A. Page (Journal of Comparative Physiology A, 2013)

A Male-Predominant Cuticular Hydrocarbon, 7-Methyltricosane, is used as a Contact Pheromone in the Western Flower Thrips Frankliniella occidentalis - Oladele A. Olaniran; Akella V. S. Sudhakar; Falko P. Drijfhout; Ian A. N. Dublon; David R. Hall; James G. C. Hamilton; William D. J. Kirk (Journal of Chemical Ecology, 2013)

Reproductive biology of squaretail coralgrouper Plectropomus areolatus using age‐based techniques - K. L. Rhodes; B. M. Taylor; C. B. Wichilmel; E. Joseph; R. J. Hamilton; G. R. Almany (Journal of Fish Biology, 2013)
The squaretail coralgrouper Plectropomus areolatus was identified as a fast‐growing, early maturing and relatively short‐lived aggregation‐spawning epinephelid. Examinations of sectioned otoliths found females and males first maturing at 2 and 3 years, respectively, suggesting protogynous hermaphroditism; however, no transitionals were observed in samples. Age distribution for the two sexes was similar and both were represented in the oldest age class; however, significant sex‐specific differences in size‐at‐age were identified. Both sexes fully recruit into the fishery at age 4 years and reach 90% of asymptotic length by age 3 years. Underwater visual assessments, combined with the gonado‐somatic indices, revealed a 5 month reproductive season, with interannual variability observed in the month of highest density within the spawning aggregation. Catch restrictions on adults during spawning times and at reproductive sites, combined with gear‐based management and enhanced enforcement, are recommended to maintain spawning stocks. Based on the available evidence, the sexual pattern for this species is unresolved.

A case study on regional impacts of climate change: peak loads on the power grid in Rochester, New York - Scott Constable; Jason Hamilton; Thomas J. Pfaff (Journal of Environmental Studies and Sciences, 2013)

Thermodesulfobacterium geofontis sp. nov., a hyperthermophilic, sulfate-reducing bacterium isolated from Obsidian Pool, Yellowstone National Park - Scott D. Hamilton-Brehm; Robert A. Gibson; Stefan J. Green; Ellen C. Hopmans; Stefan Schouten; Marcel T. J. van der Meer; John P. Shields; Jaap S. S. Damsté; James G. Elkins (Extremophiles, 2013)

Estimating global arthropod species richness: refining probabilistic models using probability bounds analysis - Andrew J. Hamilton; Vojtech Novotný; Edward K. Waters; Yves Basset; Kurt K. Benke; Peter S. Grimbacher; Scott E. Miller; G. Allan Samuelson; George D. Weiblen; Jian D. L. Yen; Nigel E. Stork (Oecologia, 2013)

Dispersal of marine benthic invertebrates through ice rafting - Colin B. A. Macfarlane; David Drolet; Myriam A. Barbeau; Diana J. Hamilton; Jeff Ollerhead (Ecology, 2013)
Knowledge of dispersal vectors used by organisms is essential to the understanding of population and community dynamics. We report on ice rafting, a vector by which intertidal benthic invertebrates can be transported well outside their normal dispersal range during winter in temperate climates. We found multiple invertebrate taxa in sediment‐laden ice blocks sampled in the intertidal zone. A large proportion of individuals were alive and active when freed from the ice. Using radio tracking, we found that ice blocks can travel over 20 km within a few days. Given the abundance of highly mobile ice blocks carrying viable invertebrates, we conclude that ice‐rafting is likely an important dispersal vector, contributing to spatial community dynamics in intertidal systems. This mechanism helps explain observed genetic structure of populations, but it also raises concerns about potential negative impacts of climate change on connectivity between populations.

A calcium-dependent interaction between calmodulin and the calponin homology domain of human IQGAP1 - William J. Andrews; Conor A. Bradley; Elaine Hamilton; Clare Daly; Thérèse Mallon; David J. Timson (Molecular and Cellular Biochemistry, 2012)

A common antifungal defense strategy in Cryptocercus woodroaches and termites - M. S. Bulmer; D. Denier; J. Velenovsky; C. Hamilton (Insectes Sociaux, 2012)

Catchment land use and trophic state impacts on phytoplankton composition: a case study from the Rotorua lakes’ district, New Zealand - Wendy J. Paul; David P. Hamilton; Ilia Ostrovsky; Steven D. Miller; Austin Zhang; Kohji Muraoka (Hydrobiologia, 2012)

Invasion facilitates hybridization with introgression in the Rattus rattus species complex - JUSTIN B. LACK; DANIEL U. GREENE; CHRIS JOHN CONROY; MEREDITH J. HAMILTON; JANET K. BRAUN; MICHAEL A. MARES; RONALD A. VAN DEN BUSSCHE (Molecular Ecology, 2012)
Biological invasions result in novel species interactions, which can have significant evolutionary impacts on both native and invading taxa. One evolutionary concern with invasions is hybridization among lineages that were previously isolated, but make secondary contact in their invaded range(s). Black rats, consisting of several morphologically very similar but genetically distinct taxa that collectively have invaded six continents, are arguably the most successful mammalian invaders on the planet. We used mitochondrial cytochrome b sequences, two nuclear gene sequences (Atp5a1 and DHFR) and nine microsatellite loci to examine the distribution of three invasive black rat lineages ( Rattus tanezumi , Rattus rattus I and R. rattus IV) in the United States and Asia and to determine the extent of hybridization among these taxa. Our analyses revealed two mitochondrial lineages that have spread to multiple continents, including a previously undiscovered population of R. tanezumi in the south‐eastern United States, whereas the third lineage ( R. rattus IV) appears to be confined to Southeast Asia. Analyses of nuclear DNA (both sequences and microsatellites) suggested significant hybridization is occurring among R. tanezumi and R. rattus I in the United States and also suggest hybridization between R. tanezumi and R. rattus IV in Asia, although further sampling of the latter species pair in Asia is required. Furthermore, microsatellite analyses suggest unidirectional introgression from both R. rattus I and R. rattus IV into R. tanezumi . Within the United States, introgression appears to be occurring to such a pronounced extent that we were unable to detect any nuclear genetic signal for R. tanezumi , and a similar pattern was detected in Asia.

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

Fish mediate high food web connectivity in the lower reaches of a tropical floodplain river - Timothy D. Jardine; Bradley J. Pusey; Stephen K. Hamilton; Neil E. Pettit; Peter M. Davies; Michael M. Douglas; Vivian Sinnamon; Ian A. Halliday; Stuart E. Bunn (Oecologia, 2012)

A community-based framework for aquatic ecosystem models - Dennis Trolle; David P. Hamilton; Matthew R. Hipsey; Karsten Bolding; Jorn Bruggeman; Wolf M. Mooij; Jan H. Janse; Anders Nielsen; Erik Jeppesen; J. Alex Elliott; Vardit Makler-Pick; Thomas Petzoldt; et al. (Hydrobiologia, 2012)

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Landsat remote sensing of chlorophyll a concentrations in central North Island lakes of New Zealand - M. G. Allan; D. P. Hamilton; B. J. Hicks; L. Brabyn (International Journal of Remote Sensing, 2011)

Rhizosphere interactions, carbon allocation, and nitrogen acquisition of two perennial North American grasses in response to defoliation and elevated atmospheric CO2 - David J. Augustine; Feike A. Dijkstra; E. William Hamilton III; Jack A. Morgan (Oecologia, 2011)

Preface: Lake restoration: an experimental ecosystem approach for eutrophication control - D. P. Hamilton; M. J. Landman (Hydrobiologia, 2011)

Research partnerships with local communities: two case studies from Papua New Guinea and Australia - G. R. Almany; R. J. Hamilton; D. H. Williamson; R. D. Evans; G. P. Jones; M. Matawai; T. Potuku; K. L. Rhodes; G. R. Russ; B. Sawynok (Coral Reefs, 2010)

Challenges and opportunities for integrating lake ecosystem modelling approaches - Wolf M. Mooij; Dennis Trolle; Erik Jeppesen; George Arhonditsis; Pavel V. Belolipetsky; Deonatus B. R. Chitamwebwa; Andrey G. Degermendzhy; Donald L. DeAngelis; Lisette N. De Senerpont Domis; Andrea S. Downing; J. Alex Elliott; Carlos Ruberto Fragoso; et al. (Aquatic Ecology, 2010)

Synthesizing mechanisms of density dependence in reef fishes: behavior, habitat configuration, and observational scale - J. Wilson White; Jameal F. Samhouri; Adrian C. Stier; Clare L. Wormald; Scott L. Hamilton; Stuart A. Sandin (Ecology, 2010)
Coral and rocky reef fish populations are widely used as model systems for the experimental exploration of density‐dependent vital rates, but patterns of density‐dependent mortality in these systems are not yet fully understood. In particular, the paradigm for strong, directly density‐dependent (DDD) postsettlement mortality stands in contrast to recent evidence for inversely density‐dependent (IDD) mortality. We review the processes responsible for DDD and IDD per capita mortality in reef fishes, noting that the pattern observed depends on predator and prey behavior, the spatial configuration of the reef habitat, and the spatial and temporal scales of observation. Specifically, predators tend to produce DDD prey mortality at their characteristic spatial scale of foraging, but prey mortality is IDD at smaller spatial scales due to attack‐abatement effects (e.g., risk dilution). As a result, DDD mortality may be more common than IDD mortality on patch reefs, which tend to constrain predator foraging to the same scale as prey aggregation, eliminating attack‐abatement effects. Additionally, adjacent groups of prey on continuous reefs may share a subset of refuges, increasing per capita refuge availability and relaxing DDD mortality relative to prey on patch reefs, where the patch edge could prevent such refuge sharing. These hypotheses lead to a synthetic framework to predict expected mortality patterns for a variety of scenarios. For nonsocial, nonaggregating species and species that aggregate in order to take advantage of spatially clumped refuges, IDD mortality is possible but likely superseded by DDD refuge competition, especially on patch reefs. By contrast, for species that aggregate socially, mortality should be IDD at the scale of individual aggregations but DDD at larger scales. The results of nearly all prior reef fish studies fit within this framework, although additional work is needed to test many of the predicted outcomes. This synthesis reconciles some apparent contradictions in the recent reef fish literature and suggests the importance of accounting for the scale‐sensitive details of predator and prey behavior in any study system.

Ophiolite Tectonics, Rock Magnetism and Palaeomagnetism, Cyprus - G. J. Borradaile; F. Lagroix; T. D. Hamilton; D.-A. Trebilcock (Surveys in Geophysics, 2010)

Race, healthcare access and physician trust among prostate cancer patients - Young Kyung Do; William R. Carpenter; Pamela Spain; Jack A. Clark; Robert J. Hamilton; Joseph A. Galanko; Anne Jackman; James A. Talcott; Paul A. Godley (Cancer Causes & Control, 2010)

NOS2A, TLR4, and IFNGR1 interactions influence pulmonary tuberculosis susceptibility in African-Americans - Digna Rosa Velez; William F. Hulme; Jamie L. Myers; J. Brice Weinberg; Marc C. Levesque; Martin E. Stryjewski; Eduardo Abbate; Rosa Estevan; Sara G. Patillo; John R. Gilbert; Carol D. Hamilton; William K. Scott (Human Genetics, 2009)

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

Mortality of developing floodplain forests subjected to a drying climate and water extraction - GILLIS J. HORNER; PATRICK J. BAKER; RALPH MAC NALLY; SHAUN C. CUNNINGHAM; JAMES R. THOMSON; FIONA HAMILTON (Global Change Biology, 2009)
River regulation and water extraction have altered the hydrology of rivers resulting in substantial changes to forest structure and the dieback of floodplain forests globally. Forest mortality, due to water extraction, is likely to be exacerbated by climate change‐induced droughts. In 1965, a plantation trial was established within a natural floodplain forest to examine the effect of planting density on timber production. We used data from this trial to investigate the effect of initial stand density on the structure and dynamics of Eucalyptus camaldulensis (Dehnh.) forests. Highest density stands (8000 trees ha −1 ) were dominated by many slender trees, mostly

Indoor/ambient residential air toxics results in rural western Montana - Tony J. Ward; Heidi Underberg; David Jones; Raymond F. Hamilton; Earle Adams (Environmental Monitoring and Assessment, 2009)

Construction dynamics of a lava channel - Andrew J. L. Harris; Massimiliano Favalli; Francesco Mazzarini; Christopher W. Hamilton (Bulletin of Volcanology, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Genetic variation in strains of zebrafish (Danio rerio) and the implications for ecotoxicology studies - T. S. Coe; P. B. Hamilton; A. M. Griffiths; D. J. Hodgson; M. A. Wahab; C. R. Tyler (Ecotoxicology, 2009)

Processes regulating the community composition and relative abundance of taxa in the diatom communities of the Malili Lakes, Sulawesi Island, Indonesia - Andrew J. Bramburger; Paul B. Hamilton; Peter E. Hehanussa; G. Douglas Haffner (Hydrobiologia, 2008)

QBO influence on extratropical predictive skill - G. J. Boer; K. Hamilton (Climate Dynamics, 2008)

Assimilatory uptake rather than nitrification and denitrification determines nitrogen removal patterns in streams of varying land use - C. P. Arango; J. L. Tank; L. T. Johnson; S. K. Hamilton (Limnology and Oceanography, 2008)
Agricultural and urban land use increase nitrogen (N) concentrations in streams, which can saturate biotic demand by plants, algae, and bacteria via assimilative uptake, and by nitrification and denitrification. We studied six streams per year in each of three land‐use categories (agricultural, urban, and forested) for 3 yr ( n = 18 streams), and we compared whole‐stream N uptake and microbial N transformation rates during spring, summer, and autumn. We measured whole‐stream removal of added ammonium (NH 4 + ) and nitrate (NO 3 − ) in the field and quantified sediment nitrification and denitrification rates in laboratory assays. Relative demand for NNH 4 + (as uptake velocity, Vf) was highest in spring and in streams with open canopies, implying a link with aquatic autotrophy. In agricultural and urban streams, whole‐stream removal (as areal uptake, U) of NH 4 + and NO 3 − , nitrification, and denitrification rates approached saturation at higher inorganic N concentrations. Nitrification and denitrification rates measured in redox‐optimized laboratory assays were roughly equivalent, suggesting that in situ redox conditions will determine whether stream sediments are a net source or sink of NO 3 − . Though nitrification and denitrification rates were measured under ideal redox conditions, they were always more than an order of magnitude lower than whole‐stream NO{3 uptake, demonstrating their limited influence on wholestream NO 3 − dynamics. Assimilatory processes, which temporarily store N removed from the water column, dominated whole‐stream N demand and controlled downstream N flux. The ultimate fate of assimilated N remains unknown; in‐channel storage cannot account for it, and thus a key question is what fraction may eventually be stored in downstream depositional zones or denitrified upon remineralization.

NO3 −-Driven SO4 2− Production in Freshwater Ecosystems: Implications for N and S Cycling - Amy J. Burgin; Stephen K. Hamilton (Ecosystems, 2008)

Effective population size dynamics reveal impacts of historic climatic events and recent anthropogenic pressure in African elephants - J. B. A. OKELLO; G. WITTEMYER; H. B. RASMUSSEN; P. ARCTANDER; S. NYAKAANA; I. DOUGLAS‐HAMILTON; H. R. SIEGISMUND (Molecular Ecology, 2008)
Two hundred years of elephant hunting for ivory, peaking in 1970–1980s, caused local extirpations and massive population declines across Africa. The resulting genetic impacts on surviving populations have not been studied, despite the importance of understanding the evolutionary repercussions of such human‐mediated events on this keystone species. Using Bayesian coalescent‐based genetic methods to evaluate time‐specific changes in effective population size, we analysed genetic variation in 20 highly polymorphic microsatellite loci from 400 elephants inhabiting the greater Samburu‐Laikipia region of northern Kenya. This area experienced a decline of between 80% and 90% in the last few decades when ivory harvesting was rampant. The most significant change in effective population size, however, occurred approximately 2500 years ago during a mid–Holocene period of climatic drying in tropical Africa. Contrary to expectations, detailed analyses of four contemporary age‐based cohorts showed that the peak poaching epidemic in the 1970s caused detectable temporary genetic impacts, with genetic diversity rebounding as juveniles surviving the poaching era became reproductively mature. This study demonstrates the importance of climatic history in shaping the distribution and genetic history of a keystone species and highlights the utility of coalescent‐based demographic approaches in unravelling ancestral demographic events despite a lack of ancient samples. Unique insights into the genetic signature of mid‐Holocene climatic change in Africa and effects of recent poaching pressure on elephants are discussed.

Regional-scale models for relating land cover to basin surface-water quality using remotely sensed data in a GIS - V. L. Versace; D. Ierodiaconou; F. Stagnitti; A. J. Hamilton; M. T. Walter; B. Mitchell; A.-M. Boland (Environmental Monitoring and Assessment, 2008)

Quantitative microbial risk assessment: uncertainty and measures of central tendency for skewed distributions - K. K. Benke; A. J. Hamilton (Stochastic Environmental Research and Risk Assessment, 2008)

Low‐dose alum application trialled as a management tool for internal nutrient loads in Lake Okaro, New Zealand - W. J. Paul; D. P. Hamilton; M. M. Gibbs (New Zealand Journal of Marine and Freshwater Research, 2008)
Aluminium sulfate (alum) was applied to Lake Okaro, a eutrophic New Zealand lake with recurrent cyanobacterial blooms, to evaluate its suitability for reducing trophic status and bloom frequency. The dose yielded 0.6 g aluminium m ‐3 in the epilimnion Before dosing, pH exceeded 8 in epilimnetic waters but was optimal for flocculation (6–8) below 4 m depth. After dosing, there was no significant change in water clarity, hypolimnetic pH decreased to 5.5 , and soluble aluminium exceeded recommended guidelines for protection of freshwater organisms. Epilimnetic phosphate concentrations decreased from 40 to 5 mg m ‐3 and total nitrogen (TN):total phosphorus (TP) mass ratios increased from 7:1 to 37:1. The dominant phytoplankton species changed from Anabaena spp. before dosing, to Ceratium hirudinella , then Staurastrum sp. after dosing. Detection of effectiveness of dosing may have been limited by sampling duration and design, as well as the low alum dose. The decrease in hypolimnetic pH and epilimnetic TP, and increase in Al 3+ and chlorophyll a , are attributed to the low alkalinity lake water and coincidence of alum dosing with a cyanobacterial bloom and high pH.

Influence of Potamogeton crispus growth on nutrients in the sediment and water of Lake Tangxunhu - W. J. Mi; D. W. Zhu; Y. Y. Zhou; H. D. Zhou; T. W. Yang; D. P. Hamilton (Hydrobiologia, 2008)

The production and emission of nitrous oxide from headwater streams in the Midwestern United States - J. J. BEAULIEU; C. P. ARANGO; S. K. HAMILTON; J. L. TANK (Global Change Biology, 2008)
The emission of nitrous oxide (N 2 O) from streams draining agricultural landscapes is estimated by the Intergovernmental Panel on Climate Change (IPCC) to constitute a globally significant source of this gas to the atmosphere, although there is considerable uncertainty in the magnitude of this source. We measured N 2 O emission rates and potential controlling variables in 12 headwater streams draining a predominantly agricultural basin on glacial terrain in southwestern Michigan. The study sites were nearly always supersaturated with N 2 O and emission rates ranged from −8.9 to 266.8 μg N 2 O‐N m −2 h −1 with an overall mean of 35.2 μg N 2 O‐N m −2 h −1 . Stream water NO 3 − concentrations best‐predicted N 2 O emission rates. Although streams and agricultural soils in the basin had similar areal emission rates, emissions from streams were equivalent to 6% of the anthropogenic emissions from soils because of the vastly greater surface area of soils. We found that the default value of the N 2 O emission factor for streams and groundwater as defined by the IPCC (EF5‐g) was similar to the value observed in this study lending support to the recent downward revision to EF5‐g. However, the EF5‐g spanned four orders of magnitude across our study sites suggesting that the IPCC's methodology of applying one emission factor to all streams may be inappropriate.

Sexual development and reproductive demography of the green humphead parrotfish (Bolbometopon muricatum) in the Solomon Islands - R. J. Hamilton; S. Adams; J. H. Choat (Coral Reefs, 2008)

Cooling lakes while the world warms: Effects of forest regrowth and increased dissolved organic matter on the thermal regime of a temperate, urban lake - Tanentzap Andrew J.; Yan Norman D.; Bill Keller; Robert Girard; Jocelyne Heneberry; John M. Gunn; David P. Hamilton; Peter A. Taylor (Limnology and Oceanography, 2008)
Depending on the magnitudes and directions of changes in air temperatures, winds, and underwater light attenuation, lakes may either warm or cool. Here we report a 28‐yr decrease in the whole‐lake average temperature of Clearwater Lake, Canada, despite regional signatures of climate warming. Using a one‐dimensional lake mixing model, we demonstrate that this pattern was attributable to a 35% reduction in surface wind speeds, itself explained by forest regrowth following local SO 2 emission reductions and tree planting, and a 10‐fold increase in dissolved organic carbon concentrations causing a substantial increase in vertical light attenuation following deacidification of the lake. Long‐term trends in lake temperatures do not necessarily follow those of air temperatures. The Clearwater Lake data demonstrate that any factors that influence local wind speeds and underwater light attenuation should be considered as modifiers of the effects of climate warming on lake thermal regimes.

Toward understanding the human dimensions of the rapidly changing arctic system: insights and approaches from five HARC projects - Henry P. Huntington; Lawrence C. Hamilton; Craig Nicolson; Ronald Brunner; Amanda Lynch; Astrid E. J. Ogilvie; Alexey Voinov (Regional Environmental Change, 2007)

Brain Uptake and Utilization of Fatty Acids, Lipids & Lipoproteins: Recommendations for Future Research - Robert Katz; James A. Hamilton; Henry J. Pownall; Richard J. Deckelbaum; Cecilia J. Hillard; Renee C. LeBoeuf; Paul A. Watkins (Journal of Molecular Neuroscience, 2007)

Brain Uptake and Utilization of Fatty Acids, Lipids and Lipoproteins: Application to Neurological Disorders - James A. Hamilton; Cecilia J. Hillard; Arthur A. Spector; Paul A. Watkins (Journal of Molecular Neuroscience, 2007)

The impact of climate change on tourism in Germany, the UK and Ireland: a simulation study - Jacqueline M. Hamilton; Richard S. J. Tol (Regional Environmental Change, 2007)

Synthesis of C-11 modified mifepristone analog libraries - Gregory L. Hamilton; Bradley J. Backes (Molecular Diversity, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Population genetic consequences of geographic disjunction: a prairie plant isolated on Great Lakes alvars - J. A. HAMILTON; C. G. ECKERT (Molecular Ecology, 2007)
Species may often exhibit geographic variation in population genetic structure due to contemporary and historical variation in population size and gene flow. Here, we test the predictions that populations on the margins of a species’ distribution contain less genetic variation and are more differentiated than populations towards the core of the range by comparing patterns of genetic variation at five microsatellite loci between disjunct and core populations of the perennial, allohexaploid herb Geum triflorum . We sampled nine populations isolated on alvar habitat within the eastern Great Lakes region in North America, habitats that include disjunct populations of several plant species, and compared these to 16 populations sampled from prairie habitat throughout the core of the species’ distribution in midwestern Canada and the USA. Alvar populations exhibited much lower within‐population diversity and contained only a subset of alleles found in prairie populations. We detected isolation by distance across the species’ range and within alvar and prairie regions separately. As predicted, genetic differentiation was higher among alvar populations than among prairie populations, even after controlling for the geographic distance between sampled populations. Low diversity and high differentiation can be accounted for by the greater contemporary spatial isolation of alvar populations. However, the genetic structure of alvar populations may also have been influenced by postglacial range expansion and contraction. Our results are consistent with alvar populations being founded during an expansion of prairie habitat during the warmer, hypsithermal period ∼5000 bp and subsequently becoming stranded on isolated alvar habitat as the climate grew cooler and wetter.

A standardized nomenclature for the mouse and rat prolactin superfamilies - Michael J. Soares; S. M. Khorshed Alam; Mary Lynn Duckworth; Nelson D. Horseman; Toshihiro Konno; Daniel I. H. Linzer; Lois J. Maltais; Marit Nilsen-Hamilton; Kunio Shiota; Jennifer R. Smith; Michael Wallis (Mammalian Genome, 2007)

Inferring climate sensitivity from volcanic events - G. J. Boer; M. Stowasser; K. Hamilton (Climate Dynamics, 2007)

Predicting tourism flows under climate change - Andrea Bigano; Jacqueline M. Hamilton; David J. Maddison; Richard S. J. Tol (Climatic Change, 2006)

Changes in markers of muscle damage, inflammation and HSP70 after an Ironman triathlon race - Katsuhiko Suzuki; Jonathan Peake; Kazunori Nosaka; Mitsuharu Okutsu; Chris R. Abbiss; Rob Surriano; David Bishop; Marc J. Quod; Hamilton Lee; David T. Martin; Paul B. Laursen (European Journal of Applied Physiology, 2006)

Protective socking material for cultivated mussels: a potential non-disruptive deterrent to reduce losses to diving ducks - Mark Dionne; Jean-Sébastien Lauzon-Guay; Diana J. Hamilton; Myriam A. Barbeau (Aquaculture International, 2006)

Analysis of the incidence of infectious pancreatic necrosis mortality in pedigreed Atlantic salmon, Salmo salar L., populations - D R Guy; S C Bishop; S Brotherstone; A Hamilton; R J Roberts; B J McAndrew; J A Woolliams (Journal of Fish Diseases, 2006)
A total of 77 124 Atlantic salmon post‐smolts, representing 197 full‐sib families produced by 149 males and 197 females, experienced a field challenge from infectious pancreatic necrosis virus (IPNV), following transfer to three separate seawater sites. The first IPN mortality was observed 45 days after transfer, and the duration of the epidemic varied between 37 and 92 days among sites. Mortalities were traced to their parental families by PIT (Passive Integrated Transpondes) tag records and DNA genotyping. Full‐sib family mean incidence of mortality was calculated for each family on each site. Heritabilities were estimated based on the heterogeneity of chi‐square using incidence within half‐sib families and the variance in incidence among full‐sib families, both on the observed and underlying liability scale. The observed correlation among families across sites was used to estimate genetic correlations. The overall mortality rate was 10.8%, with only small differences between sites, ranging from 10.3% to 11.9%. Heritabilities on the liability scale were found to be moderate to strong, and ranged between 0.24 and 0.81, with a pooled estimate of 0.43, greater than is typically associated with disease traits. Genetic correlations among sites were all substantial, between 0.71 and 0.78, and indicated that a substantial component of the genetic variation displayed within sites was common to all. The results show that field challenges can yield very good genetic information on family differences in resistance, especially when replicated over sites, which may then be developed for use in selection for breeding strains of Atlantic salmon with greater resistance to IPN.

Shorebirds, snails, and the amphipod (Corophium volutator) in the upper Bay of Fundy: top–down vs. bottom–up factors, and the influence of compensatory interactions on mudflat ecology - Diana J. Hamilton; Antony W. Diamond; Peter G. Wells (Hydrobiologia, 2006)

Empirical indices of spatial and executive processes in visuo-spatial working memory - J. M. Thompson; C. J. Hamilton; J. M. Gray; J. G. Quinn; P. Mackin; I. N. Ferrier; A. H. Young (Cognitive Processing, 2006)

Venom yields from Australian and some other species of snakes - Peter J. Mirtschin; Nathan Dunstan; Ben Hough; Ewan Hamilton; Sharna Klein; Jonathan Lucas; David Millar; Frank Madaras; Timothy Nias (Ecotoxicology, 2006)

Annual basal area increment and growth duration of Pinus taeda in response to eight years of free‐air carbon dioxide enrichment - DAVID J. P. MOORE; SUSANNE AREF; RINGO M. HO; JEFFREY S. PIPPEN; JASON G. HAMILTON; EVAN H. DE LUCIA (Global Change Biology, 2006)
Rising CO 2 is predicted to increase forest productivity, although the duration of the response and how it might be altered by variation in rainfall, temperature and other environmental variables are not well understood. We measured the basal area of rapidly growing Pinus taeda trees exposed to free‐air CO 2 enrichment for 8 years and used these measurements to estimate monthly and annual growth. We used these measurements in a statistical model to estimate the start and end of growth in each year. Elevated CO 2 increased the basal area increment ( BAI ) of trees by 13–27%. In most years, exposure to elevated CO 2 increased the growth rate but not the duration of the active growth period. With the exception of 1 year following an extreme drought and a severe ice storm, BAI was positively correlated with the amount of rainfall during the active growth period. The interannual variation in the relative enhancement of BAI caused by elevated CO 2 was strongly related to temperature and rainfall, and was greatest in years with high vapor pressure deficit. There was no evidence of a systematic reduction in the stimulation of growth during the first 8 years of this experiment, suggesting that the hypothesized limitation of the CO 2 response caused by nitrogen availability has yet to occur.

Geographical Clustering of Pancreatic Cancers in the Northeast Nile Delta Region of Egypt - A. S. Soliman; X. Wang; J.-D. Stanley; N. El-Ghawalby; M. L. Bondy; F. Ezzat; A. Soultan; M. Abdel-Wahab; O. Fathy; G. Ebidi; N. Abdel-Karim; K.-Anh. Do; et al. (Archives of Environmental Contamination and Toxicology, 2006)

The Impact of Climate on Holiday Destination Choice - Andrea Bigano; Jacqueline M. Hamilton; Richard S. J. Tol (Climatic Change, 2006)

Hinge peptide combinatorial libraries for inhilbitors of botulinum neurotoxins and saxitoxin: Deconvolution strategy - Graham J. Moore; Diana M. Moore; Samir S. Roy; Lawrence J. Hayden; Murray G. Hamilton; Nora W. C. Chan; William E. Lee (Molecular Diversity, 2006)

Does Breeding Site Fidelity Drive Phenotypic and Genetic Sub-Structuring of a Population of Arctic Charr? - Colin E. Adams; Deborah J. Hamilton; Ian Mccarthy; Alastair J. Wilson; Alan Grant; Gavin Alexander; Susan Waldron; Sigurdur S. Snorasson; Moira M. Ferguson; Skuli Skúlason (Evolutionary Ecology, 2006)

Life‐history correlates of plant invasiveness at regional and continental scales - Mark A. Hamilton; Brad R. Murray; Marc W. Cadotte; Grant C. Hose; Andrew C. Baker; Carla J. Harris; Damian Licari (Ecology Letters, 2005)
We implemented cross‐species and independent‐contrasts multiple regression models to compare life‐history correlates of invasion success between regional and continental spatial scales among non‐native plants of eastern Australia. We focussed on three life‐history traits that represent major axes of variation in plant life history: specific leaf area (SLA), plant height and seed mass. After controlling for residence time and cross‐correlation with other life‐history traits, small seed mass was significantly and uniquely correlated with invasion success at continental and regional scales. High SLA was significantly and uniquely correlated with invasion success at the continental scale only. Plant height could not explain unique variation in invasion success at either spatial scale. Variation among spatial scales in the significance and strength of life‐history relationships with invasion success suggests that the search for predictive tools of invasion need not be fruitless, as long as predictive investigations are targeted at appropriate spatial scales.

The inadvertent introduction into Australia of Trypanosoma nabiasi , the trypanosome of the European rabbit ( Oryctolagus cuniculus ), and its potential for biocontrol - P. B. HAMILTON; J. R. STEVENS; P. HOLZ; B. BOAG; B. COOKE; W. C. GIBSON (Molecular Ecology, 2005)
Wild rabbits ( Oryctolagus cuniculus ) in Australia are the descendents of 24 animals from England released in 1859. We surveyed rabbits and rabbit fleas ( Spilopsyllus cuniculi ) in Australia for the presence of trypanosomes using parasitological and PCR‐based methods. Trypanosomes were detected in blood from the European rabbits by microscopy, and PCR using trypanosome‐specific small subunit ribosomal RNA (SSU rRNA) gene primers and those in rabbit fleas by PCR. This is the first record of trypanosomes from rabbits in Australia. We identified these Australian rabbit trypanosomes as Trypanosoma nabiasi , the trypanosome of the European rabbit, by comparison of morphology and SSU rRNA gene sequences of Australian and European rabbit trypanosomes. Phylogenetic analysis places T. nabiasi in a clade with rodent trypanosomes in the subgenus Herpetosoma and their common link appears to be transmission by fleas. Despite the strict host specificity of trypanosomes in this clade, phylogenies presented here suggest that they have not strictly cospeciated with their vertebrate hosts. We suggest that T. nabiasi was inadvertently introduced into Australia in the 1960s in its flea vector Spilopsyllus cuniculi , which was deliberately introduced as a potential vector of the myxoma virus. In view of the environmental and economic damage caused by rabbits in Australia and other islands, the development of a virulent or genetically modified T. nabiasi should be considered to control rabbits.

Unusual segregation products in sperm from a pericentric inversion 17 heterozygote - Monica M. Mikhaail-Philips; Barbara C. McGillivray; Sara J. Hamilton; Evelyn Ko; Judy Chernos; Alfred Rademaker; Renée H. Martin (Human Genetics, 2005)

Identification of a Male-produced Aggregation Pheromone in the Western Flower Thrips Frankliniella occidentalis - James G. C. Hamilton; David R. Hall; William D. J. Kirk (Journal of Chemical Ecology, 2005)

Climate sensitivity and climate change under strong forcing - G. J. Boer; K. Hamilton; W. Zhu (Climate Dynamics, 2005)

Selenium in the Blackfoot, Salt, and Bear River Watersheds - S. J. Hamilton; K. J. Buhl (Environmental Monitoring and Assessment, 2005)

The ecology of sewage treatment gradients in relation to their use by waterbirds - Andrew J. Hamilton; Wayne Robinson; Iain R. Taylor; Ben P. Wilson (Hydrobiologia, 2005)

Selenium in Water, Sediment, Plants, Invertebrates, and Fish in the Blackfoot River Drainage - Steven J. Hamilton; K. J. Buhl (Water, Air, & Soil Pollution, 2004)

Inhibition of DNA alkylation damage with inorganic salts - Elizabeth E. Hamilton; Jonathan J. Wilker (JBIC Journal of Biological Inorganic Chemistry, 2004)

Carbon and nitrogen stoichiometry and nitrogen cycling rates in streams - Walter K. Dodds; Eugenia Martí; Jennifer L. Tank; Jeffrey Pontius; Stephen K. Hamilton; Nancy B. Grimm; William B. Bowden; William H. McDowell; Bruce J. Peterson; H. Maurice Valett; Jackson R. Webster; Stan Gregory (Oecologia, 2004)

Stream denitrification and total nitrate uptake rates measured using a field 15 N tracer addition approach - Patrick J. Mulholland; H. Maurice Valett; Jackson R. Webster; Steven A. Thomas; Lee W. Cooper; Stephen K. Hamilton; Bruce J. Peterson (Limnology and Oceanography, 2004)
We measured denitrification and total nitrate uptake rates in a small stream (East Fork of Walker Branch in eastern Tennessee) using a new field 15 N tracer addition and modeling approach that quantifies these rates for entire stream reaches. The field experiment consisted of an 8‐h addition of 99 atom% K 15 NO 3 and a conservative solute tracer. Two 15 N tracer addition experiments were performed on consecutive days, the first under ambient NO 3 − concentrations (23 µg N L −1 ) and the second with a NO 3 − addition of approximately 500 µg N L −1 . We fit first‐order NO 3 − uptake and two‐box denitrification models to the longitudinal measurements of tracer 15 N in dissolved NO 3 − , N 2 , and N 2 O in stream water to determine rates. Total NO 3 − uptake rates were 0.028 m −1 (0.32 µg N m −2 s −1 ) and 0.01 m −1 (1.6 µg N m −2 s −1 ) under ambient NO 3 − and with NO 3 − addition, respectively. Denitrification rates were 0.0046 m −1 (uncertainty range of 0.002 to 0.008 m −1 ) and 9×10 −5 m −1 (uncertainty range of 3 × 10 −5 to 21×10 −5 m −1 ) under ambient NO 3 − and with NO 3 − addition, respectively. Denitrification resulted almost exclusively in N 2 production (>99%) and comprised about 16% (±10%) of total NO 3 − uptake rate under ambient NO 3 − concentrations and about 1% (±1%) of total NO 3 uptake rate with NO 3 − addition. Denitrification rate expressed on a mass flux basis was about 12 µmol m −2 h −1 under ambient NO 3 − concentrations, a value within the range reported for other streams with low NO 3 − concentrations.

Evidence for a Male-Produced Sex Pheromone in the Western Flower Thrips Frankliniella occidentalis - William D. J. Kirk; James G. C. Hamilton (Journal of Chemical Ecology, 2004)

Analysis of Anal Droplets of the Western Flower Thrips Frankliniella occidentalis - Kenneth M. MacDonald; James G. C. Hamilton; Robert Jacobson; William D. J. Kirk (Journal of Chemical Ecology, 2003)

Genetic identification of two sibling species of Lutzomyia longipalpis (Diptera: Psychodidae) that produce distinct male sex pheromones in Sobral, Ceará State, Brazil - R. D. C. Maingon; R. D. Ward; J. G. C. Hamilton; H. A. Noyes; N. Souza; S. J. Kemp; P. C. Watts (Molecular Ecology, 2003)
Lutzomyia longipalpis , the main sandfly vector for New World visceral leishmaniasis is a complex of an as yet undefined number of sibling species. At present, there is no consensus on the status (single species vs. species complex) of Brazilian populations. We applied five microsatellite loci to test the hypothesis that L. longipalpis occurs as two sympatric cryptic species in Sobral, Ceará State, Brazil as predicted by male sex pheromone chemotypes described previously for field specimens from this site [ S‐ 9‐methyl‐germacrene‐B ( 9MGB) and a cembrene compound]. Abdominal spot morphology corresponds with pheromone type at this locality (9MGB in ‘1 spot’ males and cembrene in ‘2 spot’ males). Genotype data from 190 wild‐caught L. longipalpis specimens collected in October 1999 and April 2001 were used to estimate genetic differentiation between the two sex pheromone populations and sampling dates. No significant ( P > 0.05) genetic differences were found between the 1999 and 2001 9MGB samples (θ = 0.018; R ST = −0 . 005), and genetic differentiation was low between the cembrene collections (θ = 0.037, P R ST = −0.043, P > 0.05). By contrast, highly divergent allelic frequencies (largely at two microsatellite loci) corresponded to significant ( P > 0.05) genetic differentiation (θ = 0.221; R ST = 0.215) for all comparisons between samples with different pheromones. When pheromone samples were pooled across sample date, genetic differentiation was high (θ = 0.229; P N e m = 0.84). The allele frequency distribution at each of the five microsatellite loci was similar for males and females from the two collection years. Two of these loci showed highly divergent allele frequencies in the two sex pheromone populations. This was reflected in the highly significant genetic differentiation obtained from the male genotypes, between populations producing different pheromones (θ = 0.229–0.268; P P L. longipalpis .

Laboratory Dissolution Studies of Rocks from the Borrowdale Volcanic Group (English Lake District) - R. T. Stidson; J. Hamilton-Taylor; E. Tipping (Water, Air, & Soil Pollution, 2002)

Utility of Chromosomal Position of Heterochromatin as a Biomarker of Radiation-Induced Genetic Damage: A Study of Chornobyl Voles (Microtus sp.) - Lara E. Wiggins; Ronald A. Van Den Bussche; Meredith J. Hamilton; Ronald K. Chesser; Robert J. Baker (Ecotoxicology, 2002)

Cellular engineering of vascular bypass grafts: Role of chemical coatings for enhancing endothelial cell attachment - H. J. Salacinski; A. Tiwari; G. Hamilton; A. M. Seifalian (Medical & Biological Engineering & Computing, 2001)

HCO 3 - potentiates the cAMP-dependent secretory response of the human distal colon through a DIDS-sensitive pathway - Taylor J.; Hamilton K.; Butt A. (Pflügers Archiv - European Journal of Physiology, 2001)

Trace Elements in Seep Waters Along Whitewood Creek, South Dakota, and Their Toxicity to Fathead Minnows - S. J. Hamilton, K. J. Buhl (Bulletin of Environmental Contamination and Toxicology, 2000)

Characterisation of marine and lacustrine sediments in a drowned thermokarst embayment, Richards Island, Beaufort Sea, Canada - S. Solomon; P. J. Mudie; R. Cranston; T. Hamilton; S. A. Thibaudeau; E. S. Collins (International Journal of Earth Sciences, 2000)

Trace Elements in Seep Waters Along Whitewood Creek, South Dakota, and Their Toxicity to Fathead Minnows - S. J. Hamilton; K. J. Buhl (Bulletin of Environmental Contamination and Toxicology, 2000)

World‐wide genetic differentiation of Eubalaena : questioning the number of right whale species - H. C. Rosenbaum; R. L. Brownell; M. W. Brown; C. Schaeff; V. Portway; B. N. White; S. Malik; L. A. Pastene; N. J. Patenaude; C. S. Baker; M. Goto; P. B. Best; et al. (Molecular Ecology, 2000)
Few studies have examined systematic relationships of right whales ( Eubalaena spp.) since the original species descriptions, even though they are one of the most endangered large whales. Little morphological evidence exists to support the current species designations for Eubalaena glacialis in the northern hemisphere and E. australis in the southern hemisphere. Differences in migratory behaviour or antitropical distribution between right whales in each hemisphere are considered a barrier to gene flow and maintain the current species distinctions and geographical populations. However, these distinctions between populations have remained controversial and no study has included an analysis of all right whales from the three major ocean basins. To address issues of genetic differentiation and relationships among right whales, we have compiled a database of mitochondrial DNA control region sequences from right whales representing populations in all three ocean basins that consist of: western North Atlantic E. glacialis , multiple geographically distributed populations of E. australis and the first molecular analysis of historical and recent samples of E. glacialis from the western and eastern North Pacific Ocean. Diagnostic characters, as well as phylogenetic and phylogeographic analyses, support the possibility that three distinct maternal lineages exist in right whales, with North Pacific E. glacialis being more closely related to E. australis than to North Atlantic E. glacialis . Our genetic results provide unequivocal character support for the two usually recognized species and a third distinct genetic lineage in the North Pacific under the Phylogenetic Species Concept, as well as levels of genetic diversity among right whales world‐wide.

Comparative toxicity of trivalent and pentavalent inorganic and methylated arsenicals in rat and human cells - Miroslav Styblo; Luz M. Del Razo; Libia Vega; Dori R. Germolec; Edward L. LeCluyse; Geraldine A. Hamilton; William Reed; Changqing Wang; William R. Cullen; David J. Thomas (Archives of Toxicology, 2000)

Pollen‐based biome reconstruction for southern Europe and Africa 18,000 yr bp - H. Elenga; O. Peyron; R. Bonnefille; D. Jolly; R. Cheddadi; J. Guiot; V. Andrieu; S. Bottema; G. Buchet; J.‐L. De Beaulieu; A. C. Hamilton; J. Maley; et al. (Journal of Biogeography, 2000)
Pollen data from 18,000 14 C yr bp were compiled in order to reconstruct biome distributions at the last glacial maximum in southern Europe and Africa. Biome reconstructions were made using the objective biomization method applied to pollen counts using a complete list of dryland taxa wherever possible. Consistent and major differences from present‐day biomes are shown. Forest and xerophytic woods/scrub were replaced by steppe, both in the Mediterranean region and in southern Africa, except in south‐western Cape Province where fynbos (xerophytic scrub) persisted. Sites in the tropical highlands, characterized today by evergreen forest, were dominated by steppe and/or xerophytic vegetation (cf. today’s Ericaceous belt and Afroalpine grassland) at the last glacial maximum. Available data from the tropical lowlands are sparse but suggest that the modern tropical rain forest was largely replaced by tropical seasonal forest while the modern seasonal or dry forests were encroached on by savanna or steppe. Montane forest elements descended to lower elevations than today.

Ice Shelf Microbial Ecosystems in the High Arctic and Implications for Life on Snowball Earth - W. F. Vincent; J. A. E. Gibson; R. Pienitz; V. Villeneuve; P. A. Broady; P. B. Hamilton; C. Howard-Williams (The Science of Nature, 2000)

The red alga Asparagopsis taxiformis\Falkenbergia hillebrandii–a possible source of trichloroethylene and perchloroethylene? - Rhoda A. Marshall; John T. G. Hamilton; Matthew J. Dring; David B. Harper (Limnology and Oceanography, 2000)

Initial in vitro characterisation of phosphonopyruvate hydrolase, a novel phosphate starvation-independent, carbon-phosphorus bond cleavage enzyme in Burkholderia cepacia Pal6 - N. G. Ternan; J. T. G. Hamilton; J. P. Quinn (Archives of Microbiology, 2000)

Further evidence of elemental composition as an indicator of the bioavailability of humic substances to bacteria - A. P. Hunt; J. D. Parry; J. Hamilton‐Taylor (Limnology and Oceanography, 2000)
Batch culture experiments examined the ability of an isolated bacterial community to utilize four humic substances with similar molecular size but variable elemental composition. Univariate and multivariate linear regression analysis of the results provided evidence of a significant positive relationship between the N:C ratio and bacterial concentrations. In contrast, neither H:C nor O:C ratios were significant predictors of humic substances bioavailability, and their inclusion in the multivariate model provided no further explanatory power compared with the univariate model using N:C as the single independent variable. These findings suggest that N:C ratios provide the best indicator of bioavailability for complex, recalcitrant carbon moieties typical of many aquatic systems.

Expressed sequence tags derived from brain tissue of Oreochromis niloticus - L. C. Hamilton; G. R. Macpherson; J. M. Wright (Journal of Fish Biology, 2000)
Expressed sequence tags (ESTs) were obtained from complementary DNA libraries derived from the brain of the cichlid fish, Oreochromis niloticus. Single‐pass sequencing of 183 cDNA clones generated 294 ESTs; 57 of these clones (31%) were identified based on their similarity to sequences in GenBank.

Coexistence and interference between a native perennial grass and non-native annual grasses in California - J. G. Hamilton; Claus Holzapfel; Bruce E. Mahall (Oecologia, 1999)

Testing Models of Chemical Speciation in Freshwaters - S. Bryan; E. Tipping; J. Hamilton-Taylor (Environmental Geochemistry and Health, 1999)

A novel DGT‐sediment trap device for the in situ measurement of element remobilization from settling particles in water columns and its application to trace metal release from Mn and Fe oxides - J. Hamilton‐Taylor; E. J. Smith; W. Davison; H. Zhang (Limnology and Oceanography, 1999)
A device has been developed for the direct in situ measurement of metal remobilization into solution from settling particles in water columns, based on the technique of diffusion gradients in thin films (DGT). The device comprises a hollow cylinder with a DGT assembly at its base and acts as a traditional sediment trap, except that any remobilization from settling particles is reflected in the mass of metal taken up from solution by the DGT assembly. A control‐DGT device (an upside‐down trap) was used to measure the metal taken up by the assembly in the absence of remobilization from particles. Deployments of the control device under laboratory conditions and below the well‐mixed surface layer of a lake showed that the cylindrical trap design, with a height:diameter ratio of 5:1, resulted in negligible turbulence near the base of the trap so that uptake by the control was governed by molecular diffusion. The DGT‐trap and ‐control devices were deployed together within and immediately below the main oxycline of a seasonally anoxic lake in 1996 and 1997. The reproducibility of the metal uptakes measured by the devices in the field was typically better than ±10% for the controls and ±20% for the traps. The uptakes of Mn, Co, Al, Ba, and Ni, but not Fe and Cu, were significantly and consistently higher in the trap devices than in the controls. Reductive dissolution of Mn oxide appeared to be the source of the four remobilized trace metals, whereas Fe oxides made no significant contribution. The remobilization of Mn, Co, Al, Ba, and Ni was also reflected in elevated dissolved concentrations in the vicinity of the oxycline. Comparisons of the metal:Mn ratios obtained from the DGT‐trap data with those calculated from the water‐column concentrations indicated that the elevated concentrations of dissolved Co were derived solely from Mn oxide dissolution, whereas Ba, Al, and Ni also appear to be affected by other processes.

RELATIVE ABUNDANCE OF LARGE WHALES AROUND SOUTH GEORGIA (1979–1998) 1 - M. J. Moore; S. D. Berrow; B. A. Jensen; P. Carr; R. Sears; V. J. Rowntree; R. Payne; P. K. Hamilton (Marine Mammal Science, 1999)
A bstract To assess large‐whale stocks following the cessation of land‐based South Georgia whaling in 1965, we report three independent sighting databases: a cruise in 1997, observations from Bird Island (NW of South Georgia) between 1979 and 1998, and mariner sightings between 1992 and 1997. All species were rare, with sightings of southern right whales being the most common event. Two right whales photographed off South Georgia matched animals known from Peninsula Valdés, Argentina, a population known to be growing at 7% per annum . In contrast, blue and fin whales appeared to be less abundant. A single blue whale mother‐calf pair was observed off the Shag Rocks in February 1997. Extirpation of animals from this particular feeding ground is the most likely reason for ongoing low numbers of all species. Other factors may include competition for krill by traditional predators such as penguins and seals and more recently by humans, an unusually high rate of natural mortality, habitat change such as alteration in sea ice coverage, and/or the impact of ongoing whaling. The history of this critical area of large‐whale habitat and this report demonstrate the need for improved, consistent longterm monitoring of population trends for these depleted stocks.

Effects of multiple stenoses and post-stenotic dilatation on non-Newtonian blood flow in small arteries - B. Pincombe; J. Mazumdar; I. Hamilton-Craig (Medical & Biological Engineering & Computing, 1999)

The Predictability of Large Earthquakes: Evidence from an Analogue Model of Earthquake Rupture - T. Hamilton; J. McCloskey (Pure and Applied Geophysics, 1998)

Microsatellite loci reveal highly significant genetic differentiation among Atlantic salmon ( Salmo salar L.) stocks from the east coast of Canada - S. K. J. McConnell; D. E. Ruzzante; P. T. O'Reilly; L. Hamilton; J. M. Wright (Molecular Ecology, 1997)
Allele frequency data from eight microsatellite loci provide evidence of highly significant genetic differentiation among stocks of Atlantic salmon Salmo salar L. from the Bay of Fundy, eastern and north‐western Nova Scotia and Newfoundland. Estimates of genetic structure ( R ST and θ) were significant both among all samples taken from the different geographical locations and among samples from geographical regions for which more than one stock was sampled. Samples from the Bay of Fundy taken from stocks which are phenotypically and behaviourally diverse showed particularly high levels of genetic structure. Rogers', allele sharing and (δμ) 2 distances also revealed significant differences among stock samples and were significantly correlated [Rogers' and (δμ) 2 ] with sea distance between rivers. Results suggest that stocks of Atlantic salmon in eastern Canada are highly diverse genetically and that this should be an important consideration in any management programme for stocks in the area.

Spatial variability of soil total C and N and their stable isotopes in an upland Scottish grassland - C.A. Marriott; G. Hudson; D. Hamilton; R. Neilson; B. Boag; L.L. Handley; J. Wishart; C.M. Scrimgeour; D. Robinson (Plant and Soil, 1997)

Detection of methicillin-resistantStaphylococcus aureus using the BBL crystal MRSA kit - J. M. T. Hamilton-Miller (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Evidence for spatial niche partitioning in predaceous aphidophaga: Use of plant colour as a cue - F. Lorenzetti; J. T. Arnason; B. J. R. Philogène; R. I. Hamilton (BioControl, 1997)

An anoxic event and other biogeochemical effects of the Pantanal wetland on the Paraguay River - Stephen K. Hamilton; Suzanne J. Sippel; DÓbora F. Calheiros; John M. Melack (Limnology and Oceanography, 1997)
The Paraguay River was sampled throughout the annual cycle at two sites located downriver from most of the Pantanal, and major tributaries were occasionally sampled close to their entry into the Pantanal. The floodplains strongly modulate the discharge regime and substantially reduce runoff by enhancing evapotranspirative losses. Contact of the river water with the floodplain results in depletion of dissolved O 2 , oversaturation of CO 2 and CH 4 loss of suspended sediments, and reduced export of N and P. Oxygen depletion and associated chemical changes are most marked when river water first contacts the floodplain; in 1995, the water remained anoxic throughout the river channel for 6 weeks, causing massive fish mortality. Bottle incubations showed that the rate of O 2 consumption by the river water during the anoxic event was high at first (7.2 µM h −1 ) but declined exponentially over several hours and was not stimulated by organic carbon and nutrient additions. The O 2 demand may be due largely to bacterial CH 4 oxidation; the concentration of CH 4 in the river was particularly high (∼31 µ M) at the time of the incubations. The O 2 depletion corresponded with higher concentrations of most major ions, Si, and dissolved organic carbon but was not accompanied by elevated concentrations of inorganic N and P, H 2 S, or most of the 46 dissolved trace elements that were measured. In contrast to O 2 depletion and associated chemical changes, sediment retention by the floodplains was greatest at maximum river stages. Most chemical weathering of minerals seems to take place in the upland drainage basins rather than on the floodplains, and most major solutes display conservative mixing in the river‐floodplain system.

The third human isoform of 6-phosphofructo-2-kinasefructose-2,6-bisphosphatase (PFKFB3) Map position 10p14–p15 - J. Nicholl; J. A. Hamilton; G. R. Sutherland; R.L. Sutherland; C. K. W. Watts (Chromosome Research, 1997)

Improved diagnosis of cowpea aphid-borne mosaic virus in Africa: significance for cowpea seed-indexing, breeding programs and potyvirus taxonomy - C. Huguenot; M. T. Furneaux; J. A. Clare; R. I. Hamilton (Archives of Virology, 1996)

Toxicity of inorganic contaminants, individually and in environmental mixtures, to three endangered fishes (Colorado squawfish, bonytail, and razorback sucker) - K. J. Buhl; S. J. Hamilton (Archives of Environmental Contamination and Toxicology, 1996)

Toxicity of Inorganic Contaminants, Individually and in Environmental Mixtures, to Three Endangered Fishes (Colorado Squawfish, Bonytail, and Razorback Sucker) - K. J. Buhl; S. J. Hamilton (Archives of Environmental Contamination and Toxicology, 1996)

Characterization, scaling, and partial representation of diffuse and discrete input junctions to CA3 hippocampus - F. G. Ascarrunz; M. A. Kisley; K. A. Flach; R. W. Hamilton; R. J. MacGregor (Biological Cybernetics, 1995)

Characterization, scaling, and partial representation of diffuse and discrete input junctions to CA3 hippocampus - F. G. Ascarrunz; M. A. Kisley; K. A. Flach; R. W. Hamilton; R. J. MacGregor (Biological Cybernetics, 1995)

Bioaccumulation of aromatic hydrocarbons from sediments: A dose-response study with flounder (Pseudopleuronectes americanus) - J. Hellou; J.F. Payne; C. Upshall; L.L. Fancey; C. Hamilton (Archives of Environmental Contamination and Toxicology, 1994)

High level production of potyvirus-like particles in insect cells infected with recombinant baculovirus - S. J. Edwards; M. B. Hayden; R. C. Hamilton; J. A. Haynes; I. T. Nisbet; M. N. Jagadish (Archives of Virology, 1994)

Similarities in the behaviour of Chernobyl derived Ru-103, Ru-106 and Cs-137 in two freshwater lakes - J. Hilton; W. Davison; J. Hamilton-Taylor; M. Kelly; F. R. Livens; E. Rigg; D. L. Singleton (Aquatic Sciences, 1994)

Natal male baboon rank rises and successful challenges to resident alpha males - William J. Hamilton; John B. Bulger (Behavioral Ecology and Sociobiology, 1990)

Acute toxicity of boron, molybdenum, and selenium to fry of chinook salmon and coho salmon - Steven J. Hamilton; Kevin J. Buhl (Archives of Environmental Contamination and Toxicology, 1990)

Skeletal deformities in smallmouth bass,Micropterus dolomieui, from southern Appalachian reservoirs - M. J. Van Den Avyle; S. J. Garvick; V. S. Blazer; S. J. Hamilton; W. G. Brumbaugh (Archives of Environmental Contamination and Toxicology, 1989)

An immunofluorescence study of influenza virus filament formation - J. C. Cox; A. W. Hampson; R. C. Hamilton (Archives of Virology, 1980)

The replication of virulent and attenuated strains of African swine fever virus in porcine macrophages - R. C. Wardley; F. Hamilton; P. J. Wilkinson (Archives of Virology, 1979)

The growth of respiratory syncytial virus in organ cultures of bovine foetal trachea - L. H. Thomas; E. J. Stott; Jean Jebbett; Susan Hamilton (Archives of Virology, 1976)